Manipulating diffusion energy barrier in graphene oxide subnanochannels for precise radionuclide separation - Ziwen Dai; Pengrui Jin; Jing Wang; Hao Tan; Genyuan Zhang; Huying Li; Dandan Su; Sha Liang; Jiakuan Yang; Mihail Barboiu; Bart Van der Bruggen; Shushan Yuan (ENGINEERING Environment, 2026)
Nuclear energy plays a crucial role as a clean energy source in modern society. The use of nuclear energy will result in the generation of a large amount of radioactive nuclear wastewater. Separation of nuclides from radioactive wastewater is crucial for the safe disposal of nuclear wastes and the sustainable development of resources. However, it remains a great challenge to achieve precise separation between different radionuclide ions due to their similar properties. Herein, we constructed a radiation-resistant graphene-based membrane via ethylenediaminetetraacetic acid (EDTA) functionalization with highly stable and aligned two-dimensional subnanochannels, which exhibits adjustable ion diffusion energy barrier and ultrahigh radionuclide ion selectivity. The functional groups within the GO-EDTA channel exhibit strong affinitive binding interactions with Sr 2+ and La 3+ . The mono/multivalent metal-ion selectivity up to 485 and 1300 for Cs + /Sr 2+ and Cs + /La 3+ , respectively, outperforms other reported membranes. Besides, the channel can still maintain stable separation performance under irradiation conditions. Furthermore, using quartz crystal microbalance, we break down the contributions of partitioning at the pore mouth and intrapore diffusion to the overall energy barrier for salt transport, indicating that the precise separation of ions is achieved by regulating the diffusion energy barrier. This work provides a mechanism for the design of membranes with high ionion selectivity and demonstrates the application potential of nuclear resource recycling.

Textile-based solar-driven interfacial evaporation: Transport regulation, structural design, and the water-energy nexus - Xihang Xu; Xi Wang; Min Zheng; Sha Li; Songnan Zhang (Desalination, 2026)

Recharge sources and genesis of underground brines in the Mahai Basin, Qaidam Basin, China: insights from hydrochemistry and multi-isotope tracers - Ruibo Liu; Xiwei Qin; Wenquan Lu; Haiyan Shi; Zhen Shi; Chenglin Liu; Ying Ma; Xiangjun Li; Sha Yang; Ziwen Jiang; Genhou Wang; Ming Ma; et al. (Carbonates and Evaporites, 2026)

pH regulation of 1,2-bis(trimethoxysilyl)ethane hydrolysis pathways for enhanced wet state stability of TEMPO-oxidized cellulose nanofiber aerogels - Aojia Zhang; Rui Teng; Quan Zhang; Xue Liu; Biyao Sun; Chengcheng Suo; Sha Luo; Chunhui Ma; Shouxin Liu; Wei Li (Carbohydrate Polymers, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Recent advances in spinel nickel cobalt oxide-based nanostructures for oxygen electrocatalysis - He Li; Sha Qiao; Kai Fu; Liang Zhang; Jun Wang (Fuel, 2026)

Hyperspectral monitoring of wheat gluten index based on multi-model ensemble and adaptive learning - Shiyou Zhu; Juan Bai; Yulong Chen; Jingyu Chen; Caiyu Ji; Yingchao Hao; Sha Yang; Yu Zhao; Meijun Zhang; Meichen Feng; Wude Yang; Guangxin Li (Food Chemistry, 2026)

Preparation of acid-resistant sulfonated PVA/PAN pervaporation membranes for resource utilization of phosphogypsum leachate - Li Ma; Dongpu Hu; Wuqi Cai; Genyuan Zhang; Jing Wang; Yimeng Shi; Ziwen Dai; Sha Liang; Jiakuan Yang; Shushan Yuan (Desalination, 2026)

Vortex bionic structural composites fabricated by DLP 3D printing with high electromagnetic shielding effect and thermal conductive property - Jingxing Gui; Tao Zhang; Sha Long; Yingtao Li; Feiyue Zhou; Yuxuan Ma; Yuting Xue; Xueting Xu; Chunyan Hu; Baojiang Liu; Dan Yu; Wei Wang (Chemical Engineering Journal, 2026)

Role of SIRT3-mediated IDH2 deacetylation in energy metabolism disorders and necroptosis of chondrocytes induced by T-2 Toxin - Fang-Fang Yu; Yan-Jie Dou; Tong-Tong Sha; Huan-Xia Zhang; Yao Li; Qian Li; Zai-Chao Dong; Guang-Ning Kou (Chemico-Biological Interactions, 2026)

Effects of metal ions and pH on the optical properties of atmospheric brown carbon - Yu Huang; Ruoyuan Lei; Yingying Sha; Haiwei Li; Yunjiang Zhang; Junfeng Wang; Yun Wu; Ming Wang; Jianhuai Ye; Xinlei Ge (Atmospheric Pollution Research, 2026)

Honokiol Ameliorates Pyroptosis in Bovine Mammary Epithelial Cells via SIRT3-Mediated Inhibition of the NLRP3 Inflammasome - Sha Tang; Yanqiong Wen; Renxin Wu; Xing Shi; Dan Li; Siqing Mao; Xiao Yang; Hang Yu; Lei Tian; Le Zhang; Lei Liu (Tissue and Cell, 2026)

Functional exploration of mitochondrial carrier family proteins in faba bean for drought tolerance improvement - Zi-Hua Zhang; Chang-Yan Liu; Hong-Wei Chen; Li Li; Yong-Guo Zhao; Xiao-Jiao Xiang; Wen-Hui Wei; Ai-Hua Sha (Plant Science, 2026)

Reconstructing historical extreme precipitation from an aragonite-calcite stalagmite using trace-element ratios - Jiayu Lu; Haiwei Zhang; Hanying Li; Xinnan Zhao; Rui Zhang; Lijuan Sha; Jian Wang; Xiyu Dong; R. Lawrence Edwards; Hai Cheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Engineered extracellular vesicle-based microneedle patch via nose-to-brain delivery for enhanced treatment of Alzheimer's disease - Chengxue Pan; Sha Liu; Yue Zhang; Yunxia Li; Linlin Cao; Junli Zhang (Chemical Engineering Journal, 2026)

Improving dust aerosol simulation over northern China: Synergy of updated numerical models and machine learning post-processing - Tong Sha; Liangqing Li; Zipeng Dong; Qingcai Chen; Shuqi Yan; Huanxin Zhang; Jhoon Kim; Jun Wang (Atmospheric Environment, 2026)

Modified biochar-based oxidase-like catalyst for dual-signal detection of soil alkaline phosphatase - Rongcan Cai; Zhe Zhang; Qiong Li; Wenzhao Ji; Yue Li; Xudong Yang; Tong Sha; Changbao Chen; Yang Wang; Yajie Zhang (Analytica Chimica Acta, 2026)

Maize/peanut intercropping alleviates continuous peanut cropping stress via root exudate– and rhizosphere bacteria–mediated mechanisms - Zizheng Li; Li Cui; Jie Zhang; Tingting Yi; Hong Yu; Jialei Zhang; Sha Yang; Nianyuan Jiao; Feng Guo; Shubo Wan (Soil and Tillage Research, 2026)

Iteration in the evolution of hinge teeth in the cementing bivalve families Prospondylidae and Plicatulidae: Evidence from Persia (Nyalamia) n. subgen. from the lowest Jurassic of Xizang (Tibet) - Jia-Hao Li; Michael Hautmann; Qian-Qi Zhang; Hai-Chun Zhang; Jin-Geng Sha (Palaeoworld, 2026)

Triple oxygen isotope analysis of cave drip waters: insights into hydrological processes and paleoclimatic reconstruction - Lijuan Sha; Qisheng Liang; Yunxia Li; David Domínguez-Villar; Lijun Tian; Baoyun Zong; Yajie Yang; Jun-Yun Li; Haiwei Zhang; Ting-Yong Li; Hai Cheng (Geochimica et Cosmochimica Acta, 2026)

Interfacial carbon-regulated charge transfer and ROS evolution in Ag3PO4 for enhanced photo-persulfate activation - Jiaxin Li; Chunmu Yu; Yu Zhou; Xiaojuan Chen; Yi Hu; Yuyu Chen; Nianmin Bo; Xinyu Ke; Jiahao Cui; Sha Xiao; Chunhui Cui; Ziyue Yang; et al. (Environmental Research, 2026)

Improving extreme streamflow prediction by integrating CEEMDAN, autoencoders, and attention-enhanced BiLSTM optimized via GSA-PSO - Jian Sha; Jinglong Zheng; Man Zhang; Zhong-Liang Wang; Xue Li (Environmental Modelling & Software, 2026)

Atmospheric aqueous-phase reactions of organics in dark: A review - Yingying Sha; Ruoyuan Lei; Ziyan Zou; Junfeng Wang; Yunjiang Zhang; Haiwei Li; Yun Wu; Ming Wang; Xinlei Ge (Atmospheric Environment, 2026)

Inflammatory response involved in cartilage degeneration induced by T-2 toxin: systematic review - Qian Li; Yikai Hu; Juan Zuo; Zaichao Dong; Tongtong Sha; Kangting Luo; Miao Wang; Huanxia Zhang; Yanjie Dou; Shuiyuan Yu; Fang-fang Yu (Mycotoxin Research, 2026)

Combining Organic and Inorganic Amendments Simultaneously Mitigates Soil NH3 and N2O Emissions - Anrong Luo; Xiayan Zhang; Yunzhe Li; Shikang Li; Zhipeng Sha (International Journal of Environmental Research, 2026)

Distance-decay relationship reveals both horizontal and vertical dispersal limitation and source–sink relationships of phytoplankton in a deep channel-type reservoir - Xiaofeng Tang; Jian Gao; Chengying Zhang; Junyi Wu; Yaxian Wang; Sha Xu; En Hu; Sisi Ye; Chao Chang; Ming Li (ENGINEERING Environment, 2026)

Spatial reconstruction of “production-living-ecological space” and landscape ecological responses in high-density urbanization: Shanghai’s new cities - Yibei Li; Yuan Gao; Zhendong Xiao; Jingbo Wang; Guoqing Zhang; Xuan Li; Jinxia Tao; Ben Li; Jianping Yan; Zhengfeng Zhang; Jianjun Sha; Weiyue Li (Frontiers of Earth Science, 2026)

Amifostine alleviates ionizing radiation-induced small intestinal motility dysfunction in mice by remodeling the structure of the enteric nervous system - Sha-Sha Tao; Yan Li; Fei Li; Yan Wang; Meng-Ying Li; Qian Zhang; Yun-Qing Li (Histochemistry and Cell Biology, 2026)

B-MARCO: a blockchain-driven multi-national auction and resource optimization framework for cross-border logistics and trade - Mei Sha; Shuang Li; Tao Zhang; Han Liu; Jianli Shen; Xiaohu Huang; Jiahua Hu (Frontiers in Marine Science, 2026)
Cross-border maritime logistics requires coordination among carriers, ports, customs authorities, and financial institutions, yet existing workflows are often constrained by fragmented regulatory data systems, inefficient dynamic capacity matching, and slow batch-based clearing. This paper proposes B-MARCO, a blockchain-driven multi-national auction and resource optimization framework for cross-border maritime logistics. B-MARCO integrates permissioned consortium coordination, rolling auction-based market clearing, a hybrid GA-GSA dispatching engine, and privacy-preserving access-control and compliance-verification components. The evaluation uses a semi-synthetic discrete-event simulation with a 7-day horizon, hourly decision intervals, 30 random seeds, and shared order streams across all configurations. Under a 5,000-orders/day workload, B-MARCO achieves a 91.80% transaction success rate and 21.53 h average end-to-end latency, compared with 60.09% and 36.66 h for the 24-hour batch-clearing baseline. Relative to a centralized rolling-matching baseline, it reduces average latency by 13.60%. The ablation results show that rolling auction clearing reduces latency, while smart-contract-based settlement-delay reduction is a major contributor to improved success and deadline performance. These findings support the value of combining rolling market clearing with spatial-temporal dispatch optimization in simulated cross-border maritime logistics, while the blockchain and cryptographic modules define the broader coordination, auditability, and data-governance architecture.

Quantifying the light interception and canopy photosynthesis of strip intercropping system based on 3D canopy photosynthesis model - Si-Rong Huang; Qing-Feng Song; Zheng Guo; Qiu-Feng Long; Li-Sha Zhang; Yue Li; Yuan Yang; Xiao-Chun Wang; Feng Yang; Tai-Wen Yong; Jiang Liu; Yan-Hong Yan; et al. (Computers and Electronics in Agriculture, 2026)

The influence of infant temperament and family rearing environment on feeding practices in low-birth-weight infants discharged from the NICU during 6-12 months of age: A longitudinal study - Yunling Li; Shanshan Wang; Nanping Shen; Sha Sha; Xiaoli Tang; Ying Zhang (Appetite, 2026)

Intelligent identification and orientation information extraction of rock slope discontinuities from point cloud data based on LEKM-PointNet++ - Danni Zhao; Kun Li; Zixuan Zhang; Jiangbo Xu; Shengwen Qi; Peng Sha; Shaowei Wang; Guangming Luo; Bowen Zheng; Xiaolin Weng; Yalin Nan; Nengyuan Chen (Transportation Geotechnics, 2026)

A PINN-based hybrid model with APIDr for interpretable and cross-scenario landslide displacement prediction - Qing Ling; Weidong Chen; Qin Zhang; Li Wang; Wei Qu; Bao Shu; Junguang Ren; Qi Guo; Jiebo Qu; Weizhi Li; Chenjian Yang; Yiming Chen; et al. (Journal of Hydrology, 2026)

Corrigendum to Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae. Journal of Environmental Sciences (2026), doi: https://doi.org/10.1016/j.jes.2026.03.02 - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Spatial and temporal dynamics of the complexity, stability and community assembly of phytoplankton community in a deep channel-type reservoir - Xiaofeng Tang; Chengying Zhang; Sha Xu; En Hu; Chao Chang; Yuhan Ma; Daoping Xi; Ming Li (Journal of Environmental Sciences, 2026)

Hybrid H2 storage in ZIF-8 and THF-driven Hydrates: A molecular simulation study at the microsecond scale - Fengyi Mi; Hongjuan Sun; Wei Li; Bin Fang; Zhun Zhang; Bowen Sha; Thijs J.H. Vlugt; Othonas A. Moultos; Fulong Ning (Fuel, 2026)

Temperature-adaptive flexible pressure sensor based on thiol-ene click chemistry and 3D printing for wearable devices - Feiyue Zhou; Lixuan Yang; Shuqi Zhang; Yuxuan Ma; Yingtao Li; Sha Long; Dan Yu; Wei Wang (Chemical Engineering Journal, 2026)

Mechanic simulation of aquatic biodisturbation enhances phosphorus uptake and lead immobilization in paddy soils - Hui Gao; Qingnan Chu; Jun Wang; Detian Li; Jin Zhou; Wenya Hao; Min Zhang; Yumei Mao; Linkui Cao; Chengming Zhang; Zhimin Sha (Journal of Soils and Sediments, 2026)

In Vitro Release Prediction of Colchicine Transdermal Patch Based on Raman Spectroscopy Imaging and Data-Driven Modeling - Xin Sha; Wenliang Dong; Lisong Zhang; Lian Li; Wenlong Li (AAPS PharmSciTech, 2026)

Genome-wide insights into the regulatory networks of ZmHsf28 in salt and drought stress - Lijun Liu; Xia Zheng; Xiaoyu Sha; Shuaibing Tian; Ziyi Luo; Yuhan Zhang; Guocheng Wei; Yuxin Li; Jingye Fu; Qiang Wang (Plant Science, 2026)

Cover crops drive soil organic carbon sequestration in newly reclaimed saline-alkali land: Altitude and species specificity of improvement effects - Fanfan Yang; Wangrun Li; Ziting Li; Xiong Chen; Zixuan Guo; Sha Li; Wei Zhang; Gaosen Zhang; Mengmeng Zhao (Environmental Research, 2026)

Bidirectional interfacial polymerization-architected nanoporous graphene-polyamide nanofilms for efficient antibiotic separation - Yumin Sun; Yongbo Yang; Sha Liang; Yihang Zhang; Qinglin Huang; Xutong Han; Changfa Xiao; Wei Li; Kaikai Chen; Xianhui Li; Yang Yang; Hailiang Liu (Chemical Engineering Journal, 2026)

Photothermal polypyrrole-cellulose nanofiber membranes as advanced platforms for osmotic energy conversion - Wenlong Zhang; Kai Zhao; Mehraj Ahmad; Zhouyue Li; Sha Wang (Carbohydrate Polymers, 2026)

Metabolomic profiling reveals intestinal toxicity in zebrafish upon single and combined exposure to polystyrene microplastics and azithromycin - Xinwei Gao; Junyuan Li; Lukun Ge; Haichao Sha; Qi Li; Xi Li; Le Zhang; Jingnan Tan (Aquatic Toxicology, 2026)

Peroxisome proliferator-activated receptor γ coordinates the “growth-defense trade-off” in intensive aquaculture of grass carp (Ctenopharyngodon idella) - Wenting Huang; Shaoqing Zang; Hui Liu; Xinlu Ren; Ruixue Zhang; Yu Yang; Wenwen Wang; Suxu Tan; Tingting Li; Kunpeng Shi; Zhenxia Sha (Aquaculture, 2026)

Adaptive VP1 sites 93 and 97 modulate antigenic evolution and receptor binding of Senecavirus A: Phylogenetic analysis and validation with recombinant viruses - Jing Yang; Zhiliang Zhang; Weijia Sha; Mingyue Peng; Yize Li; Xiaoyu Ge; Jiaxuan Li; Wen Cui; Yanping Jiang; Xiaona Wang; Lijie Tang (Veterinary Microbiology, 2026)

Seasonal dependence of oxidative toxicity of atmospheric fine particulate matter: A case study of Xi’an, a megacity in Northwest China - Bo Wang; Qingcai Chen; Jiale Ding; Yuemei Han; Tong Sha; Qingwen Wang; Xin Zhu; Xin Zhang; Lijuan Li; Yang Li (Journal of Hazardous Materials, 2026)

Small-sized microplastics drive structural shifts in aquatic communities: Evidence from the Wei River Basin - Le Zhang; Xi Li; Qi Li; Haichao Sha; Ying Zhang; Xinwei Gao (Journal of Hazardous Materials, 2026)

Speciated emissions of full-volatility organic compounds from plastic manufacturing: atmospheric impacts and toxicity generation - Dongyang Wu; Qing’e Sha; Luyun Liu; Citao Zhang; Shan Jiang; Qing Guo; Junhao Xu; Jialin Song; Renjun Li; Liufen Cai; Haoqi Chen; Guanghui Li; et al. (Journal of Environmental Sciences, 2026)

Natural deep eutectic solvents (NADESs) as cryoprotectant for Lactiplantibacillus plantarum YR07: antifreeze mechanisms and applications - Sha sha Zheng; Li jun Tan; Qiong Pan; Yu fei Zhang; Wen di Zhang; Li fang Zou; Wei Cui; Yu Zhou; Ying ying Hu; Bao cai Xu (Food Research International, 2026)

A nanoengineered Au@Ag@PVP SERS solid-phase substrate empowered by machine learning for rapid and trace-level screening of pesticide residues in tea - Xifan Zhan; Xinying Wang; Md Mehedi Hassan; Fangling Jiang; Jiaying Xu; Yuan Zhang; Shanghua Li; Sha Zou; Hongfa Liu; Yi Xu; Quansheng Chen (Food Bioscience, 2026)

Enhance glioma treatment by bioinspired nanoplatform loaded with immunostimulants via regulation of glioma immune microenvironment - Linfeng Liu; Wei Lv; Yue Gong; Zhenwei Ding; Kefan Song; Wei Zhao; Hongli Liu; Shengnan Li; Weichong He; Jiaqing Yin; Jiangna Xu; Yuqin Chen; et al. (Chemical Engineering Journal, 2026)

miR-133a-3p promotes T-2 toxin-induced chondrocyte damage via targeting IGF1R - Kangting Luo; Lingyu Wang; Zhengyan Zhang; Yikai Hu; Chengyu Zhao; Shuiyuan Yu; Qian Li; Zaichao Dong; Tongtong Sha; Miao Wang; Juan Zuo; Yanjie Dou; et al. (Chemico-Biological Interactions, 2026)

Early Biological Orchestration in Fracture Healing: Decoding the Crosstalk between Inflammation, Coagulation, and Metabolism - Linyuan Xue; Jiyixuan Li; Minglu Hao; Sha Zhou; Ying Yang; Ting Liu; Lei Zhang; Bing Liang; Yingze Zhang; Dongming Xing (Stem Cell Reviews and Reports, 2026)

Melatonin attenuates chronic obstructive pulmonary disease by suppressing NLRP3-mediated pyroptosis in alveolar macrophages - Xiaofeng Li; Zhe Wang; Meng Shi; Tingting Zhang; Sha Huang; Xiaoju Liu (Tissue and Cell, 2026)

Quantitative study on the cave environmental factors for the fractionation of stable oxygen isotopes during the deposition of speleothem - Yue Jin; Chun-Jie Wang; Jian Zhang; Wen-Jun Sun; Chao-Jun Chen; Yao Wu; Hua-Yan Li; Yue-Hua Xiang; Yue-Yuan Lin; Xin-Rui Ye; Xin-Yan Li; Zhong-Lin Deng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Postharvest application of plasma-activated water to extend shelf life of strawberries - Yingman Gao; Yupan Zhu; Panfeng Guan; Leiyi Zhang; Xinyue Li; Guihuan Wei; Chenbin Hu; Ruichen Sha; Nanshan Du; Ruonan Ma; Zhen Jiao; Bing Li (Food Chemistry, 2026)

Histone H3K27 acetylation of slc25a4 mediates triclocarban-induced transgenerational developmental toxicity in zebrafish (Danio rerio) at subthreshold exposure - Yiming Chang; Zijian Su; Xinyi Jiang; Sihan Huang; Jialing Yu; Zhanyou Li; Keke Liu; Zhijian Sha; Lu Yang; Xiaojia Chen; An hong; Yibo Zhang; et al. (Environmental Research, 2026)

Coverage path planning for a bagging robot via spatial coordinate projection clustering of young peaches - Hongli Zhang; Jingjian Li; Fenghua Huang; Shulin Liu; Sha Wei; Haihua Xiao; Feng Ding (Computers and Electronics in Agriculture, 2026)

Genome-wide identification of the laccase gene family in wheat (Triticum aestivum L.) during Fusarium pseudograminearum infection - Li-Yu Chen; Yi Diao; Ju-Hong Ma; Xiang-Xue Zhang; Rui Li; Yan Liu; Hong-Tao Tang; Zhi Wang; Sha Gao; Rui-Huan Xu; Zhen-sheng Kang; De-Jun Han; et al. (Plant Science, 2026)

A comparative analysis of the properties of doughs prepared by liquid and firm fermentation with a co-culture of Acetobacter tropicalis A3 and Saccharomyces cerevisiae Y10 - Yanxing Wei; Yan Liu; Zongwu Zhang; Huiying Sha; Haifeng Li; Zhijian Li (Journal of Cereal Science, 2026)

Unveiling the Dual Effects of Inorganic Carbon in the CANON Process: From Essential Nutrient to Process Inhibitor and Mitigation Strategies - Sha Zhang; Dong Li; Shuai Li; Huiping Zeng; Jie Zhang (Environmental Research, 2026)

Genome-wide DNA methylation response of Paralichthys olivaceus to Ulva prolifera decomposition effluent stress - Yu Yang; Kunpeng Shi; Jie Ma; Mengyang Chang; Yishuai Li; Suxu Tan; Ruixue Zhang; Xinlu Ren; Xiaoyong Shi; Zhenxia Sha (Environmental Pollution, 2026)

Intranasal biomimetic vesicle platform reprograms the glioblastoma microenvironment for enhanced immunotherapy - Shuo Li; Chao Qin; Fan-Yu Qian; Jin-Hao Wang; Xiang-Gui Wu; Wen-Qing Li; Tai-Yu Liu; Zhao-Jie Chen; Bei-Yuan Zhang; Qi-Yue Liu; Li-Sha Liu; Li-Fang Yin (Chemical Engineering Journal, 2026)

Sulfonic acid electrolyte additives realizing high-energy-density magnesium-air batteries by pH-controlled interphase engineering and in situ protective layer construction - Wang Qiang; Sha Jianchun; Li Xue; Chen Weilong; Wang Kehao; Zhang Yusong; Yang Yiqiang; Qiao Mingliang; Tian Jie; Liu Wenhong; Zhao Zhong; Zhang Zhiqiang (Chemical Engineering Journal, 2026)

Engineered cytosolic and chloroplastic UDP-glucose epimerases distinctly modulate xylan interplay for size-tunable cellulose nanocrystals production in Oryza sativa - Yumeng Sun; Muzi Li; Meiyun Yang; Wennian Xia; Sha Wang; Zhongyi Wang; Yanting Wang; Liangcai Peng; Huizhen Hu; Ran Zhang (Carbohydrate Polymers, 2026)

Types and addition sequences of low molecular organic acids impact the remediation efficiency of cadmium-contaminated soil by biochar - Yunfeng Gao; Yang Jiang; Meiqi Chu; Xu Zhang; Yue Jiang; Jiaqi Zhang; Wei Wang; Xuesheng Liu; Sha Li; Juanjuan Qu; Hongyu Ren (Journal of Soils and Sediments, 2026)

Material source and genesis analysis of lithium-rich claystone in Balun Mahai Salt Lake, Qaidam Basin - Fan Zhang; Xiwei Qin; Yuliang Ma; Sha Yang; Tong Pan; Jianzhou Chen; Chenglin Liu; Chengwang Ding; Ziwen Jiang; Dong Zhang; Qingkuan Li; Genhou Wang; et al. (Journal of Geochemical Exploration, 2026)

Sustainable lightweight composite nanofibers: efficient control of electromagnetic pollution - Miao Li; Mengxiang Liu; Zihan Kong; Qiong Wu; Yuqi Liu; Sha Han; Tao Zhang; Xiaoxiao Huang (Journal of Cleaner Production, 2026)

Unveiling Cl-induced electrocatalytic Cα-Cβ cleavage mechanism by 1D/2D/1D TiO2@ZIS-Sv@C heterojunction for efficient aromatic aldehyde generation - Jifang Zhang; Chengcheng Suo; Hongru Zhang; Wei Li; Sha Luo; Bing Tian; Chunhui Ma; Shouxin Liu (Journal of Environmental Chemical Engineering, 2026)

CRISPR/Cas9-based evidence that overexpression of Gm-mGST1 mediates abamectin resistance in the oriental fruit moth, Grapholita molesta - Sha Su; Xiaohe Zhang; Xinyu Wang; Caiyun Qiu; Zhimin Xu; Jaime C. Piñero; Xiong Peng; Fei Li; Yayun Zuo; Maohua Chen (Insect Biochemistry and Molecular Biology, 2026)

Numerical investigation on the influence of temperature on combustion and emission characteristics of NH3/H2/CH4 mixtures under gas turbine conditions - Yanfei Zhang; Qing Hao; Mingming Huang; Zhenxian Liu; Qin Li; Zewen Yu; Jianfang Du; Xiao Zhang; Zhuoming Xiong; Qingkui Zhang; Yumeng Cao; Haoxi Sha (Fuel, 2026)

Transplantation of Skin-Derived Precursor Schwann Cells Ameliorates Secondary Brain Injury after ICH in Mice by Activating the PI3K/AKT/FOXO3a Signaling Pathway - Yuqian Tang; Yan Song; Qiuwen Sun; Muyuan Tong; Yejing Zhang; Yan Chen; Junyi Sha; Chengbin Xue; Jiabing Shen; Aihong Li (Translational Stroke Research, 2026)

Identification of TMED10 as A Regulator for Neuronal Exocytosis of Amyloid Beta 42 - Peixin Meng; Longze Sha; Xiaolin Yu; Yanbing Wang; Erning Zhang; Kexin Meng; Bingnan Li; Qin Zhao; Qi Xu (Neuroscience Bulletin, 2026)

Systematic druggable genome-wide Mendelian randomization identifies therapeutic targets for gout - Wei-quan Liao; Hui-ying Chen; Yu-ying Li; Li-juan Xiao; Zai-xing Qiu; Sha-sha Hu; Si-hui He; Lan Luo; Jing-jing Xie; Jian-yong Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

A compensatory OSB self-calibration method for user terminals when real-time PPP services lack precise code bias corrections - Xiaojie Li; Lin Pan; Cancan Wang; Hai Sha; Jinglei Guo; Lu Zhang; Yingying Zhao (Advances in Space Research, 2026)

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

Revolutionary tuned mass damper by carbon fiber powder based shear thickening fluid to realize adaptive stiffness and damping - Li Sun; Tianqi Liang; Meng Hou; Xin Sha; Chunwei Zhang (Soil Dynamics and Earthquake Engineering, 2026)

Novel phosphorus fertilizers enhance rice yield, efficiency, and environmental sustainability by optimizing soil phosphorus pools in paddy fields - Laichao Luo; Nannan Li; Wenzhuo Sha; Zhi Li; Rushan Chai; Liangliang Zhang; Chaochun Zhang; Kadambot H.M. Siddique (Soil and Tillage Research, 2026)

Distribution and potential ecological risk of para-chloro-meta-xylenol in urban lakes within a large city - Kejian Chu; Yang Zhang; Yuanyuan Sha; Yixuan Li; Qiming Li; Fuzhu Ye; Li Gu (Process Safety and Environmental Protection, 2026)

Phylogenomic framework, biogeography and character evolution of the genus Campylotropis (Fabaceae, Papilionoideae) - Li-Sha Jiang; Yu Feng; Jun-Yi Zhang; Xiong Li; Min Liao; Heng-Ning Deng; Qi Yu; Bo Xu (Molecular Phylogenetics and Evolution, 2026)

Distribution and potential risks of antibiotics in inland lakes in China - Kejian Chu; Shuo Qin; Zonghao Tian; Fuzhu Ye; Xuan Yang; Li Gu; Yuanyuan Liu; Yang Zhang; Yuanyuan Sha (Environmental Research, 2026)

Dynamic hydrolytic ion-pairing enables stable interfaces and high anode utilization in lean-electrolyte Mg-air batteries - Yuxi Zhang; Sensen Yu; Ming Li; Sha Luo; Yu Feng; An Duan; Bao Zhang; Wei Sun (Chemical Engineering Journal, 2026)

Ti3C2-Cl-Bi12O17Cl2/Bi12O17Cl2 Mott-Schottky heterojunction with mixed noncovalent/covalent type to boost ultra-sensitive photoelectrochemical sensing of ciprofloxacin - Chu-Chu Hu; Qi-E Zhang; Shao-Peng Shi; Guo-Qing Zhao; Yan-Sha Gao; Ping Liu; Xun-Kuan Ye; Yan Pan; Hui-Qing Lv; Li-Min Lu (Chemical Engineering Journal, 2026)

HIF-1α/BNIP3L–mediated mitophagy is involved in T-2 toxin–induced myocardial injury - Qian Li; Miao Wang; Juan Zuo; Zaichao Dong; Tongtong Sha; Kangting Luo; Huanxia Zhang; Yanjie Dou; Guoyu Zhou; Yue Ba; Fang-fang Yu (Chemico-Biological Interactions, 2026)

Comparison of environmental impact mitigated for Fe3O4-based nano-detergents: A life cycle perspective & scenario analysis - Xiaotong Li; Mengrong Zhang; Hanbing Li; Sha Chen; Sumei Li; Jingfu Liu (Sustainable Production and Consumption, 2025)

Water-sediment regulation drives multi-taxon biodiversity and ecological network dynamics in the Yellow River Estuary - Cheng-Rui Yan; Li-Sha Hu; Xiao-Min Zhang; Shao-Wen Li; Fan Li; Yun-Wei Dong (Regional Studies in Marine Science, 2025)

V-ATPase B mediates Bt Cry1Ac binding and toxicity in Grapholita molesta - Dandan Pan; Jiayang Feng; Jiacheng Ye; Xiaoyan Yang; Xiaoyan Zhang; Xiaofang Sha; Donghan Wang; Yanshen Fu; Chunxiao Men; Xiangqun Yuan; Yiping Li (Insect Biochemistry and Molecular Biology, 2025)

Synergistic co-encapsulation of Saccharomyces cerevisiae and Lactobacillus helveticus in water-in-water Pickering emulsion with enhanced probiotic viability and digestive resistance - Yajie Li; Jie Zhang; Sha Ao; Huaqiang Cao; Yan Li; Bin Li; Shilin Liu (Food Bioscience, 2025)

Ferritin-alginate oligosaccharide shell core complex for co-encapsulation and synergistic stabilization of astaxanthin and zinc ions - Rui Yang; Jincan Wu; Zexu Li; Yue Li; Chunkai Gu; Xinmei Sha; Li Liang; Shihao Sun; Lei Shi; Yuyu Zhang (Food Hydrocolloids, 2025)

Emission characteristics of full-volatility organic compounds from China's aluminum-products industry and their impacts on secondary organic aerosol and ozone potentials - Dongyang Wu; Qing'e Sha; Shan Jiang; Luyun Liu; Citao Zhang; Jialin Song; Junhao Xu; Haoqi Chen; Guanghui Li; Zhangmin Xiang; Bin Jiang; Zhuangmin Zhong; et al. (Environmental Research, 2025)

Deep eutectic solvent driven hydrogen bond confinement synthesis of multifunctional carbon dots from Licorice residues - Wenbo Cui; Xin Zhao; Jiali Song; Jianwei Zhao; Chunfa Zhang; Chunhui Ma; Mingcong Xu; Ruiwen Wang; Sha Luo; Shouxin Liu; Wei Li (Chemical Engineering Journal, 2025)

Plant–soil feedback alters plant–soil–microbial nutrient status and elemental-limitation status during secondary succession - Yong Cao; Zemin Ai; Xinghua Li; Mengjia Hou; Yuyan Yao; Yi Deng; Huan Liu; Jiaoyang Zhang; Guobin Liu; Sha Xue (Soil Ecology Letters, 2025)

Chronic dietary exposure to BDE-47 can induce inflammatory responses in the brain of common carp (Cyprinus carpio) and further trigger neurotoxicity through the 5-HT pathway - Huimin Sun; Youlian Liu; Yujie Huang; Mengbin Yuan; Zujun Ye; Rong Yang; Fuqiang Sha; Ni Tang; Bo Zhou; Defang Chen; Zhiqiong Li; Xin Zhang (Science of The Total Environment, 2025)

ATP synthase subunit γ mediates Cry1Ac binding and toxicity in Grapholita molesta - Jiayang Feng; Dandan Pan; Yichen Wang; Xiaoyan Zhang; Xiaofang Sha; Yanshen Fu; Jiacheng Ye; Donghan Wang; Xiangqun Yuan; Yiping Li (Pesticide Biochemistry and Physiology, 2025)

Associations of environmental toxicant exposure with adult sleep problems and the mediating roles of inflammation - Lu-Jia Li; Wen Zhang; Daniel Yee-Tak Fong; Ji-Bin Li; Yu-Hui Kou; Sha Li; Xiao-Yong Chen; Wei-Jie Gong (Environmental Pollution, 2025)

Multi-objective optimization control of a novel adaptive beam string structure with double rhombic struts: Experimental and simulation studies - Jun Zou; Jinyu Lu; Haichen Zhang; Zhicheng Sha; Jiangjun Hou; Na Li (Engineering Structures, 2025)

A Middle Devonian fluvial-delta plain complex from eastern Yunnan, South China: Insights into co-evolution between environments and organisms in an early non-marine system - Junjun Song; Xiaole Zhang; Sha Li; Wenkun Qie; Yi Wang; Honghe Xu (Earth-Science Reviews, 2025)

Spider web-inspired multifunctional aerogel sensor: MWCNT/MXene/TOCNF synergize to achieve high-sensitivity multiple detection of humidity, pressure, and photothermal stimuli - Yaoyao Ye; Xin Tong; Jiyang Zhou; Yan Zhang; Lizheng Sha; Tianzhong Yuan; Daliang Guo; Jing Li; Yonghao Ni (Chemical Engineering Journal, 2025)

Establishment of succinic acid production in recombinant Kluyveromyces marxianus enhanced by AI-guided enzyme specificity engineering and redox-controlled fermentation optimization - Du-Wen Zeng; Yi-Fan Zhu; Yuan-Hong Jiang; Ya-Hao Ding; Zhen-Zhi Wang; Kai Li; Sha Liao; Ya-Chao Fan; Lin Zhang; Yu Guang Wang; Xin-Qing Zhao (Chemical Engineering Journal, 2025)

Involvement of ductal reaction in Di-(2-ethylhexyl)-phthalate-caused hepatic fibrosis: Molecular mechanisms and potential intervention strategies - Xinru Du; Shu Zhang; Sha Liu; Yancheng Gao; Zhendong Wang; Na Dong; Sisi Song; Qinming Hui; Ziyi Wang; Yue Ma; Chunxiao Zhou; Ye Yang; et al. (Chemico-Biological Interactions, 2025)

Tianshan topographic heating and a Central Asian dipole precipitation anomaly in the mid-Holocene - Yingying Sha; Zhengguo Shi; Xiaofei Zhang; Ke Shang; Peng Zhou; Peixian Shu; Jing Lei; Xinzhou Li; Hai Cheng; Zhisheng An (Science China Earth Sciences, 2025)

Optimizing soybean production and emission reduction through biogas slurry substitution and straw incorporation: A five-year field study in northeast China's black soil region - Pingan Zhang; Aizheng Yang; Xiaofang Wang; Lihong Wang; Yan Sha; Mo Li (Agriculture, Ecosystems & Environment, 2025)

Isolation and identification of diverse steroids as Escherichia coli β -glucuronidase inhibitors from the Submerge-cultured mycelia of Hirsutella sinensis - Youmin Ying; Xiaoxiao Chen; Ling Li; Jianwei Wang; Yun Zhang; Wei Mao; Weiguang Shan; Sha Xu (Natural Product Research, 2025)

Effects of floating bed plants on remediation of eutrophic ponds and cultured species of Cyprinus carpio - Longjie Li; Mengqi He; Yingying Ge; Wanyu Wei; Minmin Wu; Yuanpu Sha; Shuwen Zhang; Jing Dong; Xuejun Li; Xiaofei Gao; Huatao Yuan (Aquaculture, 2025)

A remote sensing-based paradigm for revealing road ecological impacts in permafrost regions - Qingquan Sha; Jiawei Zhao; Lin Huang; Wei Cao; Jiahui Li; Liangxia Zhang; Yun Wang (Transportation Research Part D: Transport and Environment, 2025)

Middle Campanian to Maastrichtian foraminifera and biomarkers: Seawater incursion events in the Songliao Basin, Northeast China - Ke-Ying Yue; Sha Li; Tian Jiang; Dang-Peng Xi; Bo-Wen Song; Yu Liang; Li-Xin Sun; Tian-Fu Zhang; Hai-Chun Zhang; Xiao-Qiao Wan; Bo Wang (Palaeoworld, 2025)

Middle to late Maastrichtian planktonic foraminifera from the Gongzha section in Dingri area, southern Xizang, China - Ke-Ying Yue; Tian Jiang; Sha Li; Hai-Chun Zhang; Xiao-Qiao Wan (Palaeoworld, 2025)

Inconsistencies in global soil moisture products and discrepancies in their relationship with vegetation productivity - Xinyao Xu; Xufeng Wang; Jingfeng Xiao; Songlin Zhang; Yanpeng Yang; Xing Li; Te Sha; Zongxing Li (Journal of Hydrology, 2025)

Hydrofluoric-acid-mediated hydrothermal synthesis of anatase TiO2 with {101}/{001} facets for selective photocatalytic valorization of glycerol to syngas - Zheng Yang; Haoqiang Hou; Ermiao Liang; Kun Zhang; Mingcong Xu; Chunhui Ma; Wei Li; Sha Luo; Shouxin Liu (Journal of Environmental Chemical Engineering, 2025)

Microplastics and human health: Exposure pathways, toxicity mechanisms, and future research challenges - Zhi Wang; Nuo Li; Yongcheng Ding; Na Li; Menghan Su; Congcong Zhang; Yiqun Li; Qing Wang; Chenyan Sha; Bing Xia; Jie Cheng; Guan Jiang (Journal of Environmental Chemical Engineering, 2025)

Photocatalytic biorefining green closed-loop: Photocatalytic alkali lignin depolymerization in supramolecular solvent - Chengcheng Suo; Xiaochang Zhang; Xinai Li; Jifang Zhang; Hongru Zhang; Rui Teng; Wei Li; Sha Luo; Bing Tian; Qingjiang Pan; Chunhui Ma; Zhijun Chen; et al. (Journal of Environmental Chemical Engineering, 2025)

Hydroclimate dipole pattern in the eastern South African monsoon domain on various timescales. - Hanying Li; Shihao Lei; Lijuan Sha; Qiong Zhang; Haiwei Zhang; Jingyao Zhao; Kexin Wang; Hai Cheng (Global and Planetary Change, 2025)

Identifying gelatin source by mass spectrometry: A review - Xiao-Mei Sha; Le-Ying Yang; Hui Wang; Jie Cheng; Hao-Sheng Luo; Li-Jun Zhang; Zi-Zi Hu; Zong-Cai Tu (Food Chemistry, 2025)

The effect of uracil on the freeze-drying survival rate of Lactiplantibacillus plantarum YR07 based on transcriptome analysis - Sha-sha Zheng; Wen-di Zhang; Li-jun Tan; Li-fang Zou; Ying-ying Hu; Liu Yang; Bao-cai Xu (Food Microbiology, 2025)

Intestinal metabolomic profiling provides insights into the molecular mechanisms for hyperuricemia-induced intestinal barrier dysfunctions in a hyperuricemia mouse model - Hailong Li; Qingli Zhang; Tingting Tang; Lei Zhu; Qu Chen; Haili Zhang; Yan Zhang; Zichu Zhao; Di Xiao; Xinlei Sha; Jingrong Mu; Jingjing Kong (Food and Chemical Toxicology, 2025)

Dosimetric Comparison of Multi-Leaf and Circular Collimator-based CyberKnife Radiosurgery for Targets of Varying Size and Complexity in Intracranial, Hepatic, and Prostatic Lesions: A Comprehensive Planning Study - Bo Tian; Hui Xu; Yunfei Bian; Xiongfei Li; Sha He; Changwen Bo; Zheng Zheng; Zunhao Zhang (Journal of Medical and Biological Engineering, 2025)

Adsorption behaviors and mechanisms of azithromycin on degradable and non-degradable microplastics aged with UV/sodium percarbonate - Haichao Sha; Weinan Wang; Qi Li; Xi Li; Qinming Zhang (Journal of Water Process Engineering, 2025)

Estrogenic and transgenerational effects of perfluorocarboxylic acids through estrogen-related receptor γ pathway - Sha Shi; Wei Zheng; Xi-Long Zhang; Minjie Li; Cheng Ye; Lu Chen; Wen-Jun Hong; Chuan-Hai Li; Huiyu Chi; Fangfang Li; Liang-Hong Guo (Journal of Hazardous Materials, 2025)

Different shapes of polylactic acid bioplastic initiate intestinal injury and gut microbiota dysbiosis of zebrafish - Haichao Sha; Ji Gao; Qi Li; Xi Li; Zezhong Li; Jingwei Zhang; Xinwei Gao (Journal of Hazardous Materials, 2025)

DCNet: Full waveform inversion with difference convolution - Li-Sha Fu; Chang-Yang Hu; Leting Tan; Huawei Liao; Qiang Zhang; Fan Min (Journal of Applied Geophysics, 2025)

Function of the zasp52 gene detected by CRISPR/Cas9 in the global fruit borer Grapholita molesta - Sha Su; Zhimin Xu; Jinbo Suo; Yurong Zhou; Xiaohe Zhang; Amedius Dwigo Ignatus; Yayun Zuo; Xiong Peng; Fei Li; Maohua Chen (Insect Biochemistry and Molecular Biology, 2025)

Transcriptomic analysis and reconstruction of 2,3-butanediol catabolism for acetoin accumulation in Bacillus licheniformis - Chenxing Li; Pingjing Tian; Fengxu Xiao; Yupeng Zhang; Sipeng Yang; Siyu Li; Sha Xu; Zhongyang Ding; Liang Zhang; Youran Li; Guiyang Shi (Food Bioscience, 2025)

Protective effects of rosmarinic acid against oxidative damage and atherosclerosis via the PI3K/AKT pathway - Tiantian Tang; Mingze Sun; Baiyuan Sha; Rui Liu; Zhiyang Ren; Liwei Li; Ye Zhang; Hao Wang; Kai Yu (Food and Chemical Toxicology, 2025)

Glycine-mediated hydrogen bond network reconstruction and interfacial engineering for ultrahigh-voltage aqueous magnesium air batteries - Sha Jianchun; Liu Zhoulin; Wang Qiang; Li Xue; Yang Yiqiang; Tian Jie; Chen Weilong; Liu Wenhong; Wu Liang; Zhang Zhiqiang (Chemical Engineering Journal, 2025)

Coupling covalent organic framework with polyacrylamide to construct a robust composite hydrogel electrolyte for dendrite-free and long-lifespan aqueous zinc-ion batteries - Ziming Liu; Xiangcai Li; Heng Zhang; Xuke Zhang; Junyuan Li; Yifei Shi; Dongxiang Geng; Zhaolei Li; Dawei Sha; Genxi Yu; Chao Yan (Chemical Engineering Journal, 2025)

Charge/conformation-transformable phosphopeptide@hollow covalent organic frameworks as molecular gates for electrochemical analysis - Lin Wang; Minghui Wang; Gaoxiang Wang; Haojie Xie; Yu Hang; Dongmei Zhang; Sha Zhu; Xiafei Hu; Genxi Li (Chemical Engineering Journal, 2025)

Efficient production of ectoine from Jerusalem artichoke using engineered Escherichia coli - Hao Zhang; Hairui Tong; Qiang Yin; Yibin Qiu; Hong Xu; Sha Li (Bioresource Technology, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Study on the functional role and tissue localization of GmolTrypsin in larvae of Grapholita molesta feeding on different host plants - Dongbiao Lü; Dandan Pan; Donghan Wang; Jiacheng Ye; Xiaofang Sha; Xiaoyan Zhang; Yanshen Fu; Xiangqun Yuan; Yiping Li (Insect Biochemistry and Molecular Biology, 2025)

NPK-N application limits grain cadmium concentration of wheat via promoting Cd export during grain filling - Yiran Cheng; Yuanjiang He; Jia Chen; Weiping Li; Wenhui Xiang; Xing Chen; Dan Long; Jian Zeng; Yang Liu; Dongwei Wang; Dandan Wu; Lina Sha; et al. (Plant and Soil, 2025)

Unlocking Stress Responses: Exploring PseWRKY51 and PseWRKY60 in Pseudoroegneria libanotica Through Comprehensive Analysis of the WRKY Gene Family Under Abiotic Challenges - Xunzhe Yang; Xia Wang; Xiang Li; Chen Chen; Dandan Wu; Yiran Cheng; Yi Wang; Lina Sha; Houyang Kang; Xing Fan; Yinglong Chen; Yonghong Zhou; et al. (Journal of Plant Growth Regulation, 2025)

Identification and Characterization of LBD Gene Family in Pseudoroegneria libanotica Reveals Functions of PseLBD1 and PseLBD12 in Response to Abiotic Stress - Xunzhe Yang; Xiang Li; Xia Wang; Chen Chen; Dandan Wu; Yiran Cheng; Yi Wang; Lina Sha; Houyang Kang; Songqing Liu; Xing Fan; Yinglong Chen; et al. (Biochemical Genetics, 2025)

Root hair: An important guest-meeting avenue for rhizobia in legume–Rhizobium symbiosis - Jingwen Xiao; Wenxu Liu; Bicong Wu; Yuling Zhang; Sha Li; En Li (Plant Science, 2025)

Comparative analysis of the effects of different dimensionality reduction algorithms on hyperspectral estimation of total nitrogen content in wheat soils - Juan Bai; Shiyou Zhu; Yingchao Hao; Xinzhe Li; Chenbo Yang; Chao Wang; Xingxing Qiao; Meichen Feng; Lujie Xiao; Xiaoyan Song; Meijun Zhang; Sha Yang; et al. (European Journal of Agronomy, 2025)

A novel bioreactor developed for the intensification of high-viscosity aerobic fermentation processes - Qian Chen; Kai Hu; Quanfei Li; Kai Yang; Chao Zhang; Weiwei Huang; Yibin Qiu; Yian Gu; Liang Sun; Peng Lei; Jian Xue; Sha Li; et al. (Chemical Engineering Journal, 2025)

Dopamine-alginate-zinc ion dressings employing synergistic active and passive antimicrobial strategies for enhanced burn wound infection management and accelerated healing - Sha Zhou; Miao Zhang; Linyuan Xue; Jiyixuan Li; Xinyue Ma; Zihan Zheng; Tianrui Wang; Xiaobo Wen; Ying Yang; Saisai Yan; Qihui Zhou; Bing Liang; et al. (Carbohydrate Polymers, 2025)

Comprehensive review of ecological risks and toxicity mechanisms of microplastics in freshwater: Focus on zebrafish as a model organism - Haichao Sha; Xi Li; Qi Li; Jingwei Zhang; Ji Gao; Lukun Ge; Weinan Wang; Taotao Zeng (Aquatic Toxicology, 2025)

Electrochemical nitrite sensing using mass transfer signal with a catalyst-free small-sized rotating disk electrode for wastewater monitoring - Fengjun Yin; Xiaohui Yang; Shun Lu; Hanlin Zhang; Ying Zhao; Sha Wang; Cheng Song; Yongzhi Li; Zhaoming Chen; Hong Liu (Water Research, 2025)

Fungal Infections in Transplant Recipients Pre- and Post-coronavirus Disease 2019: Results from a Single-Center Retrospective Cohort Study - Tengteng Xin; Qinling Pan; Jiahao Li; Jing Zhang; Li Lin; Kitman Choi; Wenying Cai; Sha Lu; Junmin Zhang (Mycopathologia, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Millennial-scale climate variability of the Asian summer monsoon over the last 690,000 years: insights from cave records - Xiaowen Niu; Jian Wang; Le Kang; Youwei Li; Haiwei Zhang; Xiyu Dong; Hanying Li; Lijuan Sha; Liang Yi; Ashish Sinha; Youfeng Ning; Xue Jia; et al. (Science Bulletin, 2025)

Unexpected changes in occurrence and sources of chromophoric dissolved organic matter in PM2.5 driven by the clean air action over Xi'an, China - Xin Zhu; Qingcai Chen; Tong Sha; Yue Yin; Jinwen Li; Zimeng Zhang; Jiale Ding; Tengfei Xu (Atmospheric Environment, 2025)

Inhibition of Vascular Endothelial Growth Factor Reduces Photoreceptor Death in Retinal Neovascular Disease via Neurotrophic Modulation in Müller Glia - Shuang Gao; Sha Gao; Yanuo Wang; Lu Xiang; Hanwei Peng; Gong Chen; Jianmin Xu; Qiong Zhang; Caihong Zhu; Yingming Zhou; Na Li; Xi Shen (Molecular Neurobiology, 2025)

Comparative transcriptome analyses reveal the acute heat stress response of a cool-temperate shrimp Fenneropenaeus chinensis - Haochen Zhu; Xiaojun Zhang; Xiaoxi Zhang; Jianbo Yuan; Zhenxia Sha; Fuhua Li (Journal of Thermal Biology, 2025)

Spatial and temporal dynamics of solar energy resources in China and forecast of future solar radiation - Yong Zhou; Xueli Sha; Lingyu Wang; Xiang Li; Zhihao Zhang (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Modification of electrochemical and discharge performance of extruded Mg-3Sn-1Ca as anode for magnesium-air batteries with solid solution element Zn and Zr - Jiaxin Bao; Yusong Zhang; Lianhui Li; Jianchun Sha; Jie Tian; Xue Li; Yiqiang Yang; Wenhong Liu; Zhiqiang Zhang (Chemical Engineering Journal, 2025)

Advancements in machine learning for spatiotemporal urban on-road traffic-air quality study: A review - Zhanxia Du; Hanbing Li; Sha Chen; Xinming Zhang; Lantian Zhang; Yuting Liu (Atmospheric Environment, 2025)

Combined skin injury model from airblast overpressure and seawater immersion in rats: establishment, characterization, and mechanistic insights - Jinpeng Du; Zhao Li; Yi Kong; Wei Song; Zhongming Chen; Mengde Zhang; Yuyan Huang; Chao Zhang; Xu Guo; Linhao Hou; Yaxin Tan; Liting Liang; et al. (Journal of Molecular Histology, 2025)

Cavity as radio telescope for galactic dark photon - Yanjie Zeng; Yuxin Liu; Chunlong Li; Yuxiang Liu; Bo Wang; Zhenxing Tang; Yuting Yang; Liwen Feng; Peng Sha; Zhenghui Mi; Weimin Pan; Tianzong Zhang; et al. (Science Bulletin, 2025)

Sulfur dioxide increases testosterone biosynthesis by activating ERK1/2 pathway and disrupting autophagy in Leydig cells - Xiang Li; Yan Shi; Sha Liu; Zhiyuan Feng; Haoran Xiao; Rui Li; Zirou Li; Xinyue Zhang; Yongli Han; Jundong Wang; Chen Liang; Jian Bai; et al. (Journal of Hazardous Materials, 2025)

Identifying spatial drivers of soil heavy metal pollution risk integrating positive matrix factorization, machine learning, and multi-scale geographically weighted regression - Yujie Pan; Anmeng Sha; Wenjing Han; Chang Liu; Guowangchen Liu; Emily Welsch; Min Zeng; Shasha Xu; Yi Zhao; Shang Tian; Yiyi Li; Rui Deng; et al. (Journal of Hazardous Materials, 2025)

Provenance of Silurian sandstones in the South Kunlun terrane, West Kunlun (NW China) and the timing of the closure of the early Paleozoic Kudi-Qimanyute Ocean - Jie Zhang; Yajun Xu; Yiming Zhang; Huxiang Yang; Zihao Huang; Kai Cao; Xuguang Sha; Xin Li; Guocan Wang (Journal of Asian Earth Sciences, 2025)

In situ activatable Disulfiram-Rhodium(III) nanocomplex for Cu chelation and STAT3 inhibition to Potentiate photodynamic and immunotherapy - Yuxia Tang; Meng Dang; Yang Li; Xuan Sha; Ziqing Xu; Jie Zhang; Feiyun Wu; Shouju Wang (Chemical Engineering Journal, 2025)

Forest thinning effects on soil carbon stocks and dynamics: Perspective of soil organic carbon sequestration rates - Qing Qu; Hongwei Xu; Lin Xu; Chengming You; Bo Tan; Han Li; Li Zhang; Lixia Wang; Sining Liu; Zhenfeng Xu; Sha Xue; Minggang Wang (CATENA, 2025)

The geometry evolution of Early Paleozoic carbonate platform in the southwestern Tarim Basin, China: evidence from sequence stratigraphic analysis and seismic forward modeling - Jie Li; Zicheng Cao; Feng Geng; Suju Yang; Xuguang Sha; Mingjie Lan; Shenghou Wang; Yongchao Lu; Yangbo Lu; Daqing Tang; Zhao Zhang; Fang Hao (Frontiers in Marine Science, 2025)
Deciphering the evolution of spatial geometry of carbonate platforms in deeply buried successions is still a challenge due to the low resolution of seismic data and the constraints of drilling wells. In this study, by combining a seismic forward model, we systematically delineated the external morphology and internal architecture of seismic reflection and established a depositional model of a carbonate platform. The Lower Paleozoic strata display the high-amplitude reflection in the Lower-Middle Cambrian interval and the low-amplitude reflection in the Upper Cambrian-Middle Ordovician interval. The high-amplitude reflection interval thins or wedges out towards the center of the present Southwest Depression section, and thickens to the north and south. Inside of the high-amplitude interval, the seismic reflection terminated at the top reflector. Seismic forward modeling was performed to examine the validity of possible hypothetical models in the studied area. The modeling results show that the simulated stratigraphic patterns are comparable to a ramp or depression geometry which is well fit to the characteristics of actual seismic reflections. Such a ramp or depression geometry is built upon the changes in sea level and climate during the Cambrian period. This study emphasizes the potential of the integration of sequence stratigraphic analyses and seismic forward modeling as a seismic workflow for retrieving the stratigraphic architecture and platform geometry.

An investigation on traction for deep-sea mining vehicle considering the interference effect between adjacent grousers - Mingshuai Xi; Fei Sha; Yuhang Zuo; Jingze Xu; Siming Zhang; Zeqian Li (Ocean Engineering, 2025)

Bivalve faunal changes in Xunhua Basin shed light on the Late Miocene uplift, cooling and aridification of NE Tibetan Plateau - Jiahao Li; Bowen Song; Tingting Yu; Kexin Zhang; Junliang Ji; Thomas J. Algeo; Jingeng Sha; Sha Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Biomonitoring and food surveillance on heavy metals reveal need for food safety in a coastal region - Xin Zhang; Xiaoqian Yang; Xiaoyue Hu; Zhonghua Meng; Zhigang Yu; Zhan Sun; Ying Zhang; Zhifeng Yang; Sha Li; Jia-Sheng Wang; Qiang Jia; Lanzheng Liu; et al. (Food Research International, 2025)

Synthesis of value-added uridine 5'-diphosphate-glucose from sucrose applying an engineered sucrose synthase counteracts the activity-stability trade-off - Liting Zhao; Zhongbao Ma; Linpei Zhang; Yu Shen; Lei Chen; Youran Li; Sha Xu; Guiyang Shi; Daming Fan; Zhongyang Ding (Food Chemistry, 2025)

Creating rich closed nanopores in anthracite-derived soft carbon enables greatly-enhanced sodium-ion storage in the low-working-voltage region - Jiawei Gu; Yiwei You; Miao Liu; Ling Huang; Zhefei Sun; Junjie Liu; Liyuan Sha; Minghui Chen; Sha Li; Shunqing Wu; Qiaobao Zhang; Li Zhang (Chemical Engineering Journal, 2025)

Membrane transport engineering for efficient yeast biomanufacturing - Xin-Yue Li; Ming-Hai Zhou; Du-Wen Zeng; Yi-Fan Zhu; Feng-Li Zhang; Sha Liao; Ya-Chao Fan; Xin-Qing Zhao; Lin Zhang; Feng-Wu Bai (Bioresource Technology, 2025)

Aqueous phase photolysis of 4-nitrocatechol: Reaction kinetics, evolutions of chemical composition, light absorption and oxidation potential - Ruoyuan Lei; Yingying Sha; Haifeng Meng; Yu Huang; Jianhuai Ye; Dan Dan Huang; Yunjiang Zhang; Yun Wu; Yongjie Li; Xinlei Ge (Atmospheric Environment, 2025)

Human Umbilical Cord Mesenchymal Stem Cell-Derived Exosomes Loaded Mir-29-3p Targets AhR to Improve Juvenile Idiopathic Arthritis via Inhibiting the Expression of IL-22 in CD4+ T Cell - Xinyi Wei; Kunpeng Sui; Yuanyuan Peng; Sha Li; Yu Fang; Zhi Chen; Xiao Du; Xue Xie; Haiming Tang; QiuYue Wen; JingWei Li; Meilin He; et al. (Stem Cell Reviews and Reports, 2025)

RBM15 Knockdown Impairs the Malignancy of Cervical Cancer by Mediating m6A Modification of Decorin - Huimin Wang; Chun Li; Qiong Wei; Enjing Zhang; Yi Yang; Linlin Sha; Dan Wang (Biochemical Genetics, 2025)

Effects of astaxanthin microencapsulated from Haematococcus pluvialis on the growth, muscle quality, antioxidant system, and related gene expression of Cyprinus carpio - Yuanpu Sha; Yuhuan Chen; Jing Dong; Xiaofei Gao; Huatao Yuan; Jingxiao Zhang; Yunni Gao; Xuejun Li (Aquaculture International, 2025)

Genome-wide association study and transcriptome analysis provide the SNPs and molecular insights into the visceral nodular disease tolerance in half-smooth tongue sole (Cynoglossus semilaevis) - Mengyang Chang; Kunpeng Shi; Jinqi Xia; Ruixue Zhang; Yishuai Li; Shaoqing Zang; Suxu Tan; Wenwen Wang; Songlin Chen; Zhenxia Sha (Aquaculture, 2025)

The autotoxicity of dissolved organic matter from Microcystis may be a contributor to the decline of its bloom - Jun Sha; Lirong Song; Chao Liu; Fang Bai; Haiyang Zhang; Zichao Gong; Tianli Li; Jin Liu; Guangbin Gao; Yunlu Jia (Water Research, 2025)

Passivation mechanism to Cu and Zn in co-incineration bottom ash of dyeing sludge and rice husk via in-situ mineral regulation - Chen Dai; Sha Wan; Xiaoao Shi; Haobo Hou; Enhu Li; Jian Zhang; Yongjie Xue; Teng Wang (Journal of Cleaner Production, 2025)

Does land use change decline the regional ecosystem health maintenance? Case study in subtropical coastal region, Fuzhou, China - Zhipeng Fan; Xiaomei Li; Chaowu Yang; Hao Zhang; Xulin Guo; Shuhui Lai; Jinming Sha (Journal of Environmental Management, 2025)

Fabrication of the ferritin-mannoprotein shell-core heteroprotein complex for stabilization of bioactive molecules - Xinmei Sha; Runxuan Chen; Yichen Li; Tianyang Wang; Ku Li; Hui Guo; Yuyu Zhang; Rui Yang (Food Hydrocolloids, 2025)

Comparison of Pb adsorption and transformation behavior induced by chicken manure and its DOM in contaminated soil - Yue Jiang; Wei Yang; Jiaqi Zhang; Xuesheng Liu; Yu Jin; Sha Li; Juanjuan Qu; Wei Wang (Journal of Environmental Chemical Engineering, 2024)

1T/2H-MoS2/CdS heterojunction for the co-production of lactic acid photoreforming to hydrogen and value-added chemicals - Ermiao Liang; Xue Liu; Zheng Yang; Jifang Zhang; Yabo Qi; Rui Teng; Wenbo Cui; Mingcong Xu; Sha Luo; Chunhui Ma; Shouxin Liu; Wei Li (Journal of Environmental Chemical Engineering, 2024)

Fluorescence resonance energy transfer system coupled with photonic crystals labeling strategy for multiplexed detection of microRNAs from breast cancer - Sanxia Wang; Shixin Cai; Yi Zhao; Xin Chen; Sha Zhu; Maolin Li; Xiaoli Wang; Yuting Zhang; Nandi Zhou (Chemical Engineering Journal, 2024)

High-homogeneous recyclable self-cured epoxy resins based on imine - Changbo Zhao; Guohua Huang; Hao Zhang; Hui Xie; Feixiang Sha; Lukun Feng; Jinze Cui; Xiyan Li; Mingliang Wang; Feng Bao; Zhiyong Xue; Caizhen Zhu; et al. (Chemical Engineering Journal, 2024)

A Protocol for Body MRI/CT and Extraction of Imaging-Derived Phenotypes (IDPs) from the China Phenobank Project - Chengyan Wang; Shuo Wang; Sha Hua; Ruokun Li; Yan Li; Zhang Shi; Kai Feng; Lizhen Lan; Meng Liu; Xutong Kuang; Xueqin Xia; Shihai Zhao; et al. (Phenomics, 2024)

Capsaicin combined with stem cells improved mitochondrial dysfunction in PIG3V cells, an immortalized human vitiligo melanocyte cell line, by inhibiting the HSP70/TLR4/mTOR/FAK signaling axis - Yifei Wu; Xiaochuan Wang; Jiayu Zhang; Sha Du; Zhiqiong Wang; Jinrong Li; Wenhe Zhang; Jie Xiang; Renfu Li; Jing Liu; Xin Bi (Molecular Biology Reports, 2024)

Analysis of the temporal and spatial changes of ecological environment quality using the optimization remote sensing ecological index in the middle Yellow River Basin, China - Guanwen Li; Naichang Zhang; Yongxiang Cao; Zhaohui Xia; Chenfang Bao; Liangxin Fan; Sha Xue (Earth Science Informatics, 2024)

Unveiling the toxicological effects and risks of prometryn on red swamp crayfish (Procambarus clarkii): Health assessments, ecological, and molecular insights - Lang Zhang; Ziwei Song; Li He; Shan Zhong; Xiaoqian Ju; Hang Sha; Jing Xu; Qiuying Qin; Jie Peng; Hongwei Liang (Science of The Total Environment, 2024)

A hierarchical residual correction-based hyperspectral inversion method for soil heavy metals considering spatial heterogeneity - Yulong Wang; Bin Zou; Sha Li; Rongcai Tian; Bo Zhang; Huihui Feng; Yuqi Tang (Journal of Hazardous Materials, 2024)

In vitro digestion and fecal fermentation of Tremella fuciformis exopolysaccharides from basidiospore-derived submerged fermentation - Yan Fang; Qi Zhang; Caiyuan Yu; Xiaoqi Xu; Peng Lei; Hong Xu; Sha Li (Food Research International, 2024)

Balancing Maillard reaction products formation and antioxidant activities for improved sensory quality and health benefit properties of pan baked buns - Yao Tang; Yuan Huang; Mengru Li; Wen Zhu; Wei Zhang; Sha Luo; Yingying Zhang; Jie Ma; Yuqian Jiang (Food Research International, 2024)

Re3P4@C/TiO2 Ohmic junction Boosts charge carrier separation for photocatalytic hydrogen evolution - Jun-Wei Ji; Li-Jing Zhang; Wen-Jing Yi; Yu Wang; Jing-Huo Chen; Xin-Zheng Yue; Sha-Sha Yi (Chemical Engineering Journal, 2024)

An air-rechargeable Zn-organic battery with unprecedented fast self-charging rate - Yiqing Li; Xinin Zhang; Mi Gan; Jiangbo Sha; Yuegang Zhang; Jinzhang Liu (Chemical Engineering Journal, 2024)

Green chemistry closed-loop: Photocatalytic cleavage lignin β-O-4 bond utilizing visible light by Bi2O3/Bi2WO6 in deep eutectic solvent at room temperature - Chengcheng Suo; Jintao Yu; Jifang Zhang; Wei Li; Sha Luo; Chunhui Ma; Shouxin Liu (Biomass and Bioenergy, 2024)

Short-term usage of proton pump inhibitors during admission was associated with increased risk of rehospitalization in critically ill patients with myocardial infarction: a cohort study - Jia-De Zhu; Li-Juan Yang; Jian-Nan Zhao; Ping Wang; Yi-Hua Li; Xue-Sha Zhang; Jian-Mei Pan; Meng-Han Jiang; Hai-Ying Yang; Sun-Jun Yin; Gong-Hao He (European Journal of Clinical Pharmacology, 2024)

Inhaled delivery of cetuximab-conjugated immunoliposomes loaded with afatinib: A promising strategy for enhanced non-small cell lung cancer treatment - Sha Liu; Daoyuan Chen; Xiaosu Zhu; Xiaowen Wang; Xiao Li; Yuan Du; Peng Zhang; Jingwei Tian; Yingjian Song (Drug Delivery and Translational Research, 2024)

Ambient ultrafine particles exacerbate oxygen desaturation during sleep in patients with chronic obstructive pulmonary disease: New insights into the effect spectrum of ultrafine particles on susceptible populations - Wenlou Zhang; Baiqi Chen; Yoshiko Yoda; Masayuki Shima; Chen Zhao; Xuezhao Ji; Junyi Wang; Sha Liao; Simin Jiang; Luyi Li; Yahong Chen; Xinbiao Guo; et al. (Science of The Total Environment, 2024)

The resistance mechanism of humic acids and proteins in soluble microbial products from activated sludge against silver nanoparticles - Jia Kang; Yi-hang Wang; Yao-wen Zhang; Chu-qiong Song; Ao-di Wang; Ning Zhou; Yi-hui Zhang; Fa-zhan Li; Shu-li Liu; Li-sha Liu; Gang-fu Song; Bai-hong Wang (Journal of Environmental Chemical Engineering, 2024)

A new glycoprotein from pigeon egg: Study on its structure and digestive characteristics - Yu Xiao; Zeyun Zhao; Tao Zhang; Xiaoqi Xu; Khan Anik; Yibin Qiu; Zheng Xu; Sha Li; Hong Xu (Food Research International, 2024)

Casein phosphopeptide interferes the interactions between ferritin and ion irons - Xinmei Sha; Lei Zhu; Huimin Wu; Yue Li; Jincan Wu; Haotong Zhang; Yuyu Zhang; Rui Yang (Food Chemistry, 2024)

Multilevel regulation of lactose operon in Bacillus licheniformis: Coordination of LacR, CcpA and TnrA regulators - Siyu Li; Fengxu Xiao; Hehe He; Yupeng Zhang; Pengyang Liu; Ying Xu; Lihuang Zhang; Sha Xu; Zhongyang Ding; Guiyang Shi; Youran Li (Food Bioscience, 2024)

Adaptive shifts in constructed wetland microbial communities and GHG emissions under different NPs concentrations disturbances - Xinyue Zhao; Tuoshi Zhang; Ming Jin; Aiqi Sha; Wei Li; Ning Hou (Chemical Engineering Journal, 2024)

Development of wheat-tetraploid Thinopyrum elongatum 4EL small fragment translocation lines with stripe rust resistance gene Yr4EL - Biran Gong; Jing Gao; Yangqiu Xie; Hao Zhang; Wei Zhu; Lili Xu; Yiran Cheng; Yi Wang; Jian Zeng; Xing Fan; Lina Sha; Haiqin Zhang; et al. (Theoretical and Applied Genetics, 2024)

Parametric analysis on mechanical performance and additional reinforcement design method of reinforced concrete chimneys with openings - Zhi-Qian Dong; Gang Li; Song-Ke Zhang; Sha-Yi Wang; Ding-Hao Yu; Zeng-Bo Yao; Chun-Gang Liu; Mei Yang (Bulletin of Earthquake Engineering, 2024)

Levels, sources, and health risk assessment of phthalate acid esters in indoor dust of various microenvironments in university - Jun Pan; Xin Li; Ping Ding; Haojie Luo; Sha Cai; Qing Ge; Liuyi Zhang; Guocheng Hu (Chemosphere, 2024)

Computational microfluidics of reactive transport processes with solid dissolution and self-induced multiphase flow - Chuangde Zhang; Li Chen; Xin Sha; Qinjun Kang; Zhenxue Dai; Wen-Quan Tao (Advances in Water Resources, 2024)

NSP4 promotes replication of porcine reproductive and respiratory syndrome virus-2 - Hang Zhang; Gan Li; Yajie Zheng; Qin Luo; Huiyang Sha; Wenchao Sun; Mengmeng Zhao (Veterinary Microbiology, 2024)

Dual pathways of aragonite-to-calcite transformation in stalagmites: Implications for paleoclimate reconstructions - Rui Zhang; Haiwei Zhang; Christoph Spötl; Hai Cheng; Yanjun Cai; Carlos Pérez-Mejías; Xiyu Dong; Lijuan Sha; Youwei Li; Liangcheng Tan; Jingjie Zang; Xunlin Yang; et al. (Geochimica et Cosmochimica Acta, 2024)

Enhancement of efficient molecular biology tools for Tremella fuciformis spore - Caiyuan Yu; Yuanwei Sun; Chunkai Yang; Yan Fang; Qi Meng; Yibin Qiu; Peng Lei; Hong Xu; Qi Zhang; Sha Li (Food Bioscience, 2024)

Adenylate kinase phosphate energy shuttle underlies energetic communication in flagellar axonemes - Huan Wu; Yanman Zhang; Yuqian Li; Shuya Sun; Jintao Zhang; Qingsong Xie; Yue Dong; Shushu Zhou; Xuan Sha; Kuokuo Li; Jinyi Chen; Xin Zhang; et al. (Science China Life Sciences, 2024)

High dimensional proteomic mapping of bone marrow immune characteristics in immune thrombocytopenia - Feng-Qi Liu; Qing-Yuan Qu; Ying Lei; Qi Chen; Yu-Xiu Chen; Meng-Lin Li; Xue-Yan Sun; Ye-Jun Wu; Qiu-Sha Huang; Hai-Xia Fu; Yuan Kong; Yue-Ying Li; et al. (Science China Life Sciences, 2024)

Diatoms as indicators of environmental change in coastal areas: a case study in Lianjiang coast of East China Sea - Tong Li; Jihui Zhang; Dongling Li; Chengxu Zhou; Chenxi Liu; Hao Xu; Bing Song; Longbin Sha (Acta Oceanologica Sinica, 2024)

Are vacuolar dynamics crucial factors for plant cell division and differentiation? - Ya-Nan Wu; Jin-Yu Lu; Sha Li; Yan Zhang (Plant Science, 2024)

Transcriptional modulation of the global regulator CodY using a conditional CRISPRi system in Bacillus licheniformis - Lihuan Zhang; Youran Li; Fengxu Xiao; Yupeng Zhang; Liang Zhang; Zhongyang Ding; Zhenghua Gu; Sha Xu; Guiyang Shi (Systems Microbiology and Biomanufacturing, 2024)

Climatic response to solar activity recorded in the Eocene varves from Qaidam Basin, northern Tibetan Plateau - Lei Zhang; Ya-Nan Fang; Yi-Zhe Wang; Nai-Hua Xue; Sha Li; Lei Chen; Hai-Chun Zhang (Palaeoworld, 2024)

LTA and PGN from Bacillus siamensis can alleviate soybean meal-induced enteritis and microbiota dysbiosis in Lateolabrax maculatus - Zi-Yan Liu; Hong-Ling Yang; Guo-He Cai; Sha Li; Ji-Dan Ye; Chun-Xiao Zhang; Yun-Zhang Sun (Fish & Shellfish Immunology, 2024)

Enhancing hydrological extremes prediction accuracy: Integrating diverse loss functions in Transformer models - Xue Li; Qi-Liang Sun; Yanfei Zhang; Jian Sha; Man Zhang (Environmental Modelling & Software, 2024)

Boosting electrocatalytic activity of Ru for hydrogen evolution through engineering Ru on multiple interfaces of 1T-MoS2 and carbon - Changyi Xu; Huizhen Yu; Huamei Huang; Wanchun Huang; Sha Li; Yinghuan Cao; Haifeng Lu; Guimei Li; Yejin Li; Xiaokun Li; Youlin Zhang; Wei Chen (Chemical Engineering Journal, 2024)

Arabidopsis Sar1b is critical for pollen tube growth - Xin Liang; Shi-Hao Zhu; Qiang-Nan Feng; Sha Li; Yan Zhang (Plant Molecular Biology, 2024)

Metagenomic Next-Generation Sequencing Contributes to the Early Diagnosis of Mixed Infections in Central Nervous System - Li Lin; Junyue Fang; Jiahao Li; Ying Tang; Tengteng Xin; Nengtai Ouyang; Wenying Cai; Lisi Xie; Sha Lu; Junmin Zhang (Mycopathologia, 2024)

Transcriptomic analysis reveals molecular characterization and immune landscape of PANoptosis-related genes in atherosclerosis - Zhipeng Zheng; Kaiyuan Li; Zhiyuan Yang; Xiaowen Wang; Cheng Shen; Yubin Zhang; Huimin Lu; Zhifeng Yin; Min Sha; Jun Ye; Li Zhu (Inflammation Research, 2024)

The application of ferritin in transporting and binding diverse metal ions - Jincan Wu; Yue Li; Huimin Wu; Haotong Zhang; Xinmei Sha; Junrui Ma; Rui Yang (Food Chemistry, 2024)

Effect of water-induced changes in molecular structure and vapor pressure on the heterogeneous hygrothermal degradation of konjac glucomannan - Yuanyuan Chen; Xinshuai Zhang; Sha Li; Ding An; Hongshan Liang; Bin Li; Jing Li (Food Hydrocolloids, 2024)

Poly(vinylidene fluoride)-based composite membranes with continuous metal–organic framework layer for high-performance separators of lithium-ion batteries - Mengying Li; Sha Cheng; Jisong Zhang; Cheng Huang; Jiapei Gu; Jin Han; Xu Xu; Xiao Chen; Pengchao Zhang; Ya You (Chemical Engineering Journal, 2024)

Development of a stable genetic transformation system in Erigeron breviscapus: a case study with EbYUC2 in relation to leaf number and flowering time - Qin Zhu; Ying-Chun Lu; Jing-Lei Xiong; Yun-Hui Yang; Jian-Li Yang; Sheng-Chao Yang; Guang-Hui Zhang; Ben-Cai Sha; Si-Mei He (Planta, 2024)

Genome constitution and evolution of Elymus atratus (Poaceae: Triticeae) inferred from cytogenetic and phylogenetic analysis - Lu Tan; Dan-Dan Wu; Chang-Bing Zhang; Yi-Ran Cheng; Li-Na Sha; Xing Fan; Hou-Yang Kang; Yi Wang; Hai-Qin Zhang; Marcial Escudero; Yong-Hong Zhou (Genes & Genomics, 2024)

The association between per-/polyfluoroalkyl substances in serum and thyroid function parameters: A cross-sectional study on teenagers living near a Chinese fluorochemical industrial plant - Lin-Na Xie; Xiao-Chen Wang; Li-Qin Su; Sai-Sai Ji; Wen Gu; Holly Barrett; Xiao-Jie Dong; Hui-Juan Zhu; Sha-Sha Hou; Zhen-Huan Li; Yi-Lin Liu; Ling Zhang; et al. (Science of The Total Environment, 2024)

Water-sediment regulation affects community structures of macrobenthic mollusks in the Yellow River estuary and adjacent waters - Li-Sha Hu; Xiao-Min Zhang; Shao-Wen Li; Fan Li; Yun-Wei Dong (Regional Studies in Marine Science, 2024)

Arabidopsis HAPLESS13/AP-1µ is critical for pollen sac formation and tapetal function - Gui-Min Yin; Yi-Ru Fang; Jia-Gang Wang; Yue Liu; Xiaojiao Xiang; Sha Li; Yan Zhang (Plant Science, 2024)

The prolamins, from structure, property, to the function in encapsulation and delivery of bioactive compounds - Xinmei Sha; Haili Sun; Yue Li; Jincan Wu; Haotong Zhang; Rui Yang (Food Hydrocolloids, 2024)

Changes in sources and formation mechanisms of carbonaceous aerosols driven by short-term air pollution controls in Megacity Xi'an, China - Zimeng Zhang; Tong Sha; Zhen Mu; Jinwen Li; Zipeng Dong; Dyussenova Ainur; Jiale Ding; Xingxing Jiang; Tengfei Xu; Qingcai Chen (Atmospheric Environment, 2024)

Genome-wide identification and quantification of salinity-responsive Na+/K+-ATPase α-subunits in three salmonids - Yue Su; Shuang-En Yu; Yong-Xu Sun; Liang Zhang; Yue Tan; Yu-Yang Zhang; Shuo Wang; Yan-Gen Zhou; Li-Sha Hu; Yun-Wei Dong (Aquaculture, 2024)

Revolutionizing soil heavy metal remediation: Cutting-edge innovations in plant disposal technology - Yucheng Hu; Junbang Wang; Yongsheng Yang; Sha Li; Qinghua Wu; Eugenie Nepovimova; Xiujuan Zhang; Kamil Kuca (Science of The Total Environment, 2024)

Rolling with the punches: Organism-environment interactions shape spatial pattern of adaptive differentiation in the widespread mantis shrimp Oratosquilla oratoria - Jiao Cheng; Zhixin Zhang; Yulong Li; Liwen Zhang; Min Hui; Zhongli Sha (Science of The Total Environment, 2024)

Ni-Pt nanozyme-mediated relaxation and colorimetric sensor for dual-modality detection of norovirus - Lei Huang; Xue Zhang; Zefeng Mao; Sha Liu; Yanchun Li; Shuyue Ren; Huanying Zhou; Baolin Liu; Zhixian Gao (Science of The Total Environment, 2024)

LA-ICPMS in situ U Pb dating of skarn garnet from the Tongling ore district of eastern China - Ting Liang; Shao-Bing Zhang; Xiao-Yong Yang; Zhen-Xin Li; Xing-Yu Yao; Yu Wang; Sha-Sha Liu (Lithos, 2024)

Ligand doping engineering induced robust internal electric field in MOFs/BiVO4 photoanode for water splitting - Jun-Wei Ji; Li-Jing Zhang; Hai-Chao Wang; Yan-Xin Duan; Xin-Zheng Yue; Jing-Huo Chen; Sha-Sha Yi (Chemical Engineering Journal, 2024)

High-solution emission characters and health risks of volatile organic compounds for sprayers in automobile repair industries - Zhanxia Du; Hanbing Li; Lei Nie; Zhen Yao; Xinmin Zhang; Yuting Liu; Sha Chen (Environmental Science and Pollution Research, 2024)

Efficient prediction of SOC and aggregate OC components by continuous wavelet transform spectra under different feature selection methods - Sha Yang; Zhigang Wang; Caiyu Ji; Yingchao Hao; Zihao Liang; Xiaobin Yan; Xingxing Qiao; Meichen Feng; Lujie Xiao; Xiaoyan Song; Meijun Zhang; Guangxin Li; et al. (Computers and Electronics in Agriculture, 2024)

PLZF protein forms a complex with protein TET1 to target TCF7L2 in undifferentiated spermatogonia - Xiaomin Du; Donghui Yang; Xiuwei Yu; Yudong Wei; Wenbo Chen; Yuanxin Zhai; Fanglin Ma; Mengfei Zhang; Shicheng Wan; Yunxiang Li; Xinchun Yang; Aili Aierken; et al. (Theriogenology, 2024)

Middle to late Eocene charophytes from the Gaize Basin in central Tibet - Yi Xing; Sha Li; Bowen Song; Gaolei Jiang; Yi Wei; Fang Han; Kexin Zhang (Review of Palaeobotany and Palynology, 2024)

Highly effective synthesis of novel structured phospholipid emulsifiers using magnetically recyclable Fe3O4@SiO2/M (M = Zn or Al) composite - Jia Ma; Jiang-Hua Zhang; Hua-Wei Zhang; Qian-Qian Du; Zi-Xuan Li; Zhi-Fei Yang; Sha-Sha Yang; Da-Yong Zhou (Food Chemistry, 2024)

Enhanced O/W emulsion stability and betanin protection using yeast protein and chitooligosaccharide: Comparative insights from complex coacervation and layer-by-layer methods - Jiangnan Hu; Rui Yang; Runxuan Chen; Chang Liu; Xinmei Sha; Ku Li; Hui Guo; Yuyu Zhang (Food Hydrocolloids, 2024)

Paraprobiotic and postbiotic forms of Bacillus siamensis improved growth, immunity, liver and intestinal health in Lateolabrax maculatus fed soybean meal diet - Zi-Yan Liu; Hong-Ling Yang; Sha Li; Guo-He Cai; Ji-Dan Ye; Chun-Xiao Zhang; Yun-Zhang Sun (Fish & Shellfish Immunology, 2024)

Suitable biochar application practices simultaneously alleviate N2O and NH3 emissions from arable soils: A meta-analysis study - Xiayan Zhang; Lipeng Gu; Dongyang Gui; Bing Xu; Rui Li; Xian Chen; Zhipeng Sha; Xuejun Pan (Environmental Research, 2024)

3D network of zinc powder woven into fibre filaments for dendrite-free zinc battery anodes - Lin Sha; Bin-Bin Sui; Peng-Fei Wang; Zhe Gong; Yu-Hang Zhang; Yu-Han Wu; Li-Na Zhao; Jun-Jie Tang; Fa-Nian Shi (Chemical Engineering Journal, 2024)

TET1 Regulates Proliferation of Mouse Skin-Derived Stem Cells In Vitro - Tian Qiao; Li Li; Ming-Xin Zang; Yi-Nuo Jiang; Sha-Sha Wang; Chun-Xiao Li; Xin-Xiang Xie; Geng Zhang; Ying Zhang; Wei Ge; Wei Shen; Shun-Feng Cheng (Stem Cell Reviews and Reports, 2024)

Stay in touch with the endoplasmic reticulum - Sha Sun; Gan Zhao; Mingkang Jia; Qing Jiang; Shulin Li; Haibin Wang; Wenjing Li; Yunyun Wang; Xin Bian; Yan G. Zhao; Xun Huang; Ge Yang; et al. (Science China Life Sciences, 2024)

A spatial weather generator based on conditional deep convolution generative adversarial nets (cDCGAN) - Jian Sha; Xinyu Chen; Yaxin Chang; Man Zhang; Xue Li (Climate Dynamics, 2024)

Histone methyltransferase KMT2D inhibits ENKTL carcinogenesis by epigenetically activating SGK1 and SOCS1 - Yue-Hua Zhang; Qing Tao; Wen-Yan Zhang; Sha Zhao; Wei-Ping Liu; Li-Min Gao (Genes & Genomics, 2024)

A spatial projection pursuit model for identifying comprehensive urban vitality on blocks using multisource geospatial data - Zhiran Zhang; Jiping Liu; Chengyu Wang; Yangyang Zhao; Xizhi Zhao; Pengpeng Li; Dexuan Sha (Sustainable Cities and Society, 2024)

Mitigation of reactive nitrogen loss from arable soils through microbial inoculant application: A meta-analysis - Jiyang Lv; Xiayan Zhang; Zhipeng Sha; Shouguo Li; Xian Chen; Yongliang Chen; Xuejun Liu (Soil and Tillage Research, 2024)

Using a two-step downscaling method to assess the impact of climate change on total nitrogen load in a small basin - Xue Li; Yingyin Zhou; Jian Sha; Man Zhang; Zhong-Liang Wang (Journal of Hydrology, 2024)

Surface sediment diatoms in the northern and middle Okinawa Trough and their correlation with environmental variables - Chipeng He; Bin Zhai; Tong Li; Zhilei Sun; Dongling Li; Xilin Zhang; Hao Xu; Xiaodong Yang; Longbin Sha (Journal of Asian Earth Sciences, 2024)

Mercury contents and isotope ratios in marine and terrestrial archives across the Cretaceous/Paleocene boundary - Sha Li; Stephen E. Grasby; Yi Xing; Edmund A. Jarzembowski; Qifei Wang; Haichun Zhang; Xiaoqiao Wan; Bo Wang (Earth-Science Reviews, 2024)

Efficient piezo-photocatalysis of Bi2O2(OH)NO3/BiOI heterojunction: Collaboration of piezoelectric polarization and interface electric field - Yuanrui Li; Xiaolei Zhang; Rui Sha; Tong Li; Cheng Hu; Shuchen Tu; Fang Chen; Hongwei Huang (Chemical Engineering Journal, 2024)

Quantifying threshold and scale response of urban air and surface temperature to surrounding landscapes under extreme heat - Xinyu Bai; Zhaowu Yu; Benyao Wang; Yanting Zhang; Siqi Zhou; Xiaohan Sha; Siheng Li; Xihan Yao; Xiaolei Geng (Building and Environment, 2024)

High Lewis acidity catalyst for direct depolymerization of microcrystalline cellulose to 5- hydroxymethylfurfural: Reaction optimization by central composite design - Yu Yin; Chunhui Ma; Wei Li; Sha Luo; Zhanshuo Zhang; Shouxin Liu (Biomass and Bioenergy, 2024)

Effects of degradation level and vegetation recovery age on soil erodibility of alpine grasslands on the Qinghai−Tibetan Plateau - Yuanze Li; Bingbing Lu; Huakun Zhou; Yue Zhang; Ziwen Zhao; Wenjing Chen; Yang Wu; Ziqi Guo; Jun Jiang; Sha Xue (Journal of Soils and Sediments, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Toxicological evaluation of TBBPA by common carp (Cyprinus carpio) about the in vivo/vitro disturbance of the AHR pathway - Renjun Wang; Chen Zhang; Xingyang Li; Weilai Sha; Zhenhong Xue; Zhiguang Zhou; Yongchao Ma; Shuyun Zhu; Zitong Guo; Bin Zhao; Wanglong Zhang (Science of The Total Environment, 2023)

JAZ1 gene regulates starch biosynthesis and changes physicochemical properties in wheat grains - Sha-Sha Yuan; Peng Fan; Dan-Dan Zhang; Hai-Tao Liu; Peng-Fei Wang; Tian-Cai Guo; Ge-Zi Li; Yong-Hua Wang; Guo-Zhang Kang (Food Bioscience, 2023)

In vitro gastrointestinal digestion of thermally reversible and irreversible fish gelatin induced by microbial transglutaminase - Xiao-Mei Sha; Ting Fang; Jia-Hui Zhang; Sheng Shu; Wen-Li Jiang; Zi-Zi Hu; Zong-Cai Tu (Food Hydrocolloids, 2023)

Arabidopsis Sar1 isoforms play redundant roles in female gametophytic development - Xin Liang; Shan-Wei Li; Jin-Li Wang; Hui-Min Zhao; Sha Li; Yan Zhang (Plant Reproduction, 2023)

Histological Assessment and Transcriptome Analysis Provide Insights into the Toxic Effects of Perfluorooctanoic Acid to Juvenile Half Smooth Tongue Sole Cynoglossus semilaevis - Min Zhan; Kunpeng Shi; Xue Zhang; Qingxin Fan; Qian Xu; Xinbao Liu; Zhujun Li; Hongning Liu; Yanting Xia; Zhenxia Sha (Journal of Ocean University of China, 2023)

Dietary nano-selenium improves health of liver and intestine of grass carp Ctenopharyngodon idella after overwintering - Limin Ye; Sha Liu; Xiaotian Zhang; Chi Wang; Pengju Li; Cheng Zhang; Hong Ji; Haibo Yu (Animal Feed Science and Technology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Boerechalasins A–G, cytochalasans from the fungus Boeremia exigua with anti-inflammatory and cytotoxic activities - Si-Qiong Teng; Xiao-Fang Zhang; Hong-Fei Li; Xin-Wen Luo; Yang-Sha Zhou; Hui Liu; Ji-Kai Liu; Tao Feng (Phytochemistry, 2023)

Interrogating greenhouse gas emissions of different dietary structures by using a new food equivalent incorporated in life cycle assessment method - Mengrong Zhang; Hanbing Li; Sha Chen; Yingying Liu; Sumei Li (Environmental Impact Assessment Review, 2023)

Carrier-free 5-Fu nanoparticle-mediated domestication therapy for scar treatment: A preclinical and first-in-human study - Peng He; Sha Yi; Jianzhong Zhang; Chengchao Chu; Xuqi Peng; Changhong Li; Xinfei Sun; Yang Zhang; Hongwei Cheng; Xia Xiong; Gang Liu (Chemical Engineering Journal, 2023)

The association of garlic intake and cardiovascular risk factors: A systematic review and meta-analysis - Sha Li; Wei Guo; Winnie Lau; Hui Zhang; Zhongqun Zhan; Xiaonan Wang; Hui Wang (Critical Reviews in Food Science and Nutrition, 2023)

Phase change materials in food: Phase change temperature, environmental friendliness, and systematization - Chi Hu; Lishan Sha; Chongxing Huang; Wanru Luo; Bo Li; Haohe Huang; Chenglong Xu; Kaikai Zhang (Trends in Food Science & Technology, 2023)

Signaling between sporophytic integuments and developing female gametophyte during ovule development - Zheng Qin; Ya-Nan Wu; Sha Li; Yan Zhang (Plant Science, 2023)

Removal of low-concentration tetracycline from water by a two-step process of adsorption enrichment and photocatalytic regeneration - Jianyu Xing; Jumei Huang; Xi Wang; Feiying Yang; Yuehao Bai; Sha Li; Xinhao Zhang (Journal of Environmental Management, 2023)

Effects of phenolic acid analogs on the structure, iron oxidation/iron release, and stability of phytoferritin - Jiangnan Hu; Lina Shi; Lei Zhu; Xinmei Sha; Yue Li; Junrui Ma; Qing Zhang; Rui Yang (Food Bioscience, 2023)

Probiotic components of Bacillus siamensis LF4 mitigated β-conglycinin caused cell injury via modulating TLR2/MAPKs/NF-κB signaling in Lateolabrax maculatus - Zi-Yan Liu; Hong-Ling Yang; Sha Li; Guo-He Cai; Ji-Dan Ye; Chun-Xiao Zhang; Yun-Zhang Sun (Fish & Shellfish Immunology, 2023)

Ni-CeO2 nanocomposite with enhanced metal-support interaction for effective ammonia decomposition to hydrogen - Hongwang Liu; Yining Zhang; Sibao Liu; Sha Li; Guozhu Liu (Chemical Engineering Journal, 2023)

α2,3-Sialylation with Fucosylation Associated with More Severe Anti-MDA5 Positive Dermatomyositis Induced by Rapidly Progressive Interstitial Lung Disease - Rongrong Zhang; Li Guo; Jichen Sha; Shuwai Chang; Jiangfeng Zhao; Kaiwen Wang; Jiucun Wang; Jianxin Gu; Jing Liu; Shifang Ren (Phenomics, 2023)

Epidemiology and Clinical Findings of Tinea Capitis: A 23-Year Retrospective, Single-Center Study in Guangzhou, China - Wenying Cai; Junhao Huang; Jiahao Li; Li Lin; Liyan Xi; Junmin Zhang; Xiqing Li; Zhen Zhou; Ying Tang; Hsingmei Liu; Jing Zhang; Sha Lu (Mycopathologia, 2023)

Supervised Mineral Prospectivity Mapping via Class-Balanced Focal Loss Function on Imbalanced Geoscience Datasets - Zhiqiang Zhang; Yingjie Li; Gongwen Wang; Emmanuel John M. Carranza; Shuren Yang; Deming Sha; Junjie Fan; Xiang Zhang; Yulong Dong (Mathematical Geosciences, 2023)

Sources and health risk assessment of water-soluble and water-insoluble metals in road and foliar dust in Xi'an, Northwest China - Qingwen Wang; Qingcai Chen; Chao Wang; Ruihe Wang; Tong Sha; Qian Zhang; Yanguang Li (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Effect of plant-soil feedback on soil microbial co-occurrence network depends on the stage of secondary succession - Zemin Ai; Yi Deng; Xinghua Li; Jiaoyang Zhang; Hongfei Liu; Hongwei Xu; Guobin Liu; Xue Sha (Rhizosphere, 2023)

Removal of Microcystis aeruginosa and its extracellular organic matters by using covalently bonded coagulant: An alternative choice in enhanced coagulation for algae-polluted water treatment - Yong Nie; Rui Zhang; Sha Li; Wei Xia; Jiangya Ma (Journal of Cleaner Production, 2023)

Improving air quality through urban form optimization: A review study - Sha Li; Bin Zou; Xuying Ma; Ning Liu; Zixin Zhang; Manman Xie; Lu Zhi (Building and Environment, 2023)

Has Arctic sea ice loss affected summer precipitation in North China? - Bingyi Wu; Zhenkun Li; Xiang Zhang; Yuqing Sha; Xinrong Duan; Xueqi Pang; Shuoyi Ding (International Journal of Climatology, 2023)
Arctic sea ice loss is one of the most striking features in changing of the climate system and affects weather and climate in the midlatitudes through complex interactions and feedback processes. However, it is not clear whether Arctic sea ice loss has affected summer precipitation in East Asia. This study shows that summer regional precipitation in North China exhibits obvious features of phasic variations. Before 1998, positive and negative precipitation anomalies appeared alternately. While from 1999 to 2011, negative precipitation anomalies were dominant. Since 2012, increased summer precipitation has been observed frequently. A direct cause of increases of summer precipitation in North China is an enhancement of water vapour transport from South China and China's marginal seas, which can be attributed to the strengthening and northward shifting of the northwestern Pacific subtropical high and the spatial configuration with west low–east high and north low–south high in East Asian height fields. Although summer atmospheric circulation anomalies in high latitudes are dominant during the sea ice melting phase, their contributions to summer precipitation variations in North China are little. Simulation experiments show that Arctic sea ice loss can significantly affect the atmospheric circulation in high latitudes; however, it cannot be regarded as a major cause of observed recent increases in precipitation in North China. Additionally, Arctic sea ice loss has little impact on summer precipitation in the Yangtze River valley and South China.

Acer truncatum leaves reduce lipid accumulation and improve liver and intestine health of grass carp (Ctenopharyngodon idella) fed with high-fat diet - Limin Ye; Xiaotian Zhang; Chi Wang; Sha Liu; Pengju Li; Cheng Zhang; Qinfeng Gao; Hong Ji; Haibo Yu (Aquaculture, 2023)

CRISPR/Cas9-mediated BoaAOP2s editing alters aliphatic glucosinolate side-chain metabolic flux and increases the glucoraphanin content in Chinese kale - Hao Zheng; Wenli Huang; Xiangxiang Li; Huanhuan Huang; Qiao Yuan; Ruobin Liu; Hongmei Di; Sha Liang; Mengyu Wang; Mengyao Li; Zhi Huang; Yi Tang; et al. (Food Research International, 2023)

Self-assembly of porous cellulose fibers and the incorporation of graphene carbon quantum dots for stable luminescence - Xin Zhang; Youliang Cheng; Sha Wang; Changqing Fang; Jing Chen; Mengyao Li; Weina Zhao (Carbohydrate Polymers, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Efficiently activating peroxymonosulfate by CoFe-LDHs/MoS2 for rapid degradation of tetracycline - Jingyang Li; Haiyu Cao; Hongying Qi; Yuexiang Li; Sha Zhu; Xue Ye; Jintao Zhang; Zifeng Yu; Jiao Zhu; Xin Zhao (Journal of Water Process Engineering, 2023)

Association of multiple air pollutants with oxygen saturation during sleep in COPD patients: Effect modification by smoking status and airway inflammatory phenotypes - Wenlou Zhang; Junyi Wang; Baiqi Chen; Xuezhao Ji; Chen Zhao; Maike Chen; Sha Liao; Simin Jiang; Zihan Pan; Wanzhou Wang; Luyi Li; Yahong Chen; et al. (Journal of Hazardous Materials, 2023)

Cation-deficient T-Nb2O5/graphene Hybrids synthesized via chemical oxidative etching of MXene for advanced lithium-ion capacitors - Lei Wang; Xiong Zhang; Chen Li; Yanan Xu; Yabin An; Wenjie Liu; Tao Hu; Sha Yi; Kai Wang; Xianzhong Sun; Yue Gong; Zhong-Shuai Wu; et al. (Chemical Engineering Journal, 2023)

Sn2+/Mn2+ co-doped germanate glass with quasi-sunlight spectrum visible-emission and its high-quality w-LED application - Yuhang Zhang; Baojiu Chen; Xizhen Zhang; Yongze Cao; Jinsu Zhang; Sai Xu; Xiangping Li; Hongquan Yu; Duan Gao; Xuezhu Sha; Li Wang; Xin Chen; et al. (Chemical Engineering Journal, 2023)

Novel PbO@C composite material directly derived from spent lead-acid batteries by one-step spray pyrolysis process - Wenhao Yu; Mingyang Li; Sha Liang; Qi Xu; Peiyuan Zhang; Huijie Hou; Jingping Hu; Jiakuan Yang (Waste Management, 2023)

Commensal Bacillus siamensis LF4 ameliorates β-conglycinin induced inflammation in intestinal epithelial cells of Lateolabrax maculatus - Zi-Yan Liu; Hong-Ling Yang; Xi-Yue Ding; Sha Li; Guo-He Cai; Ji-Dan Ye; Chun-Xiao Zhang; Yun-Zhang Sun (Fish & Shellfish Immunology, 2023)

Functionalized graphitic carbon nitride based catalysts in solar-to-chemical conversion for hydrogen peroxide production - Chao Liang; Xue-Min Wang; Wei Liu; Hui-Yun Liu; Da-Wei Huang; Yuan-Zheng Zhang; Kai-Hang Zhang; Li-Sha Jiang; Yu-Yu Jia; Cheng-Gang Niu (Chemical Engineering Journal, 2023)

Superior triethylamine sensing platform based on MOF activated by carbon dots for photoelectric dual-mode in biphasic system - Xue-Chun Yang; Sha-Qi Fu; Qian-Li Li; Zheng Jiao; Jing-Tai Zhao; Yun Guo; Zhi-Jun Zhang; Song Gao; Ling-Li Cheng (Chemical Engineering Journal, 2023)

Liver transcriptome analysis and identification of differentially expressed immune gene response to Aeromonas veronii infection in Channa argus - Xiumei Chen; Jiasong Zhang; Muyang Li; Jiaxin Tian; Xiaotian Niu; Xiaofeng Shan; Sha Luo; Guiqin Wang; Aidong Qian (Aquaculture International, 2023)

Detection of Alternaria alternata infection in winter jujubes based on optical properties and their correlation with internal quality parameters during storage - Mengwei Jiang; Sicong You; Hao Sha; Bingyao Bai; Li Zhang; Kang Tu; Jing Peng; Lijun Song; Weijie Lan; Leiqing Pan (Food Chemistry, 2023)

Regulating robust interphase using a functional ionic liquid additive with bi-electrode affinity to stabilize the high-voltage lithium-rich lithium metals batteries - Jiaqi Huang; Haitao Zhang; Xuedi Yuan; Yifan Sha; Jin Li; Tao Dong; Yuting Song; Suojiang Zhang (Chemical Engineering Journal, 2023)

Fertilizers inclusion with nitrification inhibitors alleviate soil CO2 emissions: a meta-analysis study - Shouguo Li; Zhipeng Sha; Xiayan Zhang; Jiyang Lv; Xian Chen; Qiliang Yang (Journal of Soils and Sediments, 2023)

Microplastic sink that cannot be ignored in chemosynthetic organisms - Kangning Zhang; Junhua Liang; Zhongli Sha; Li Zhou; Shan Zheng; Xiaoxia Sun (Marine Pollution Bulletin, 2023)

Manganese and copper additions differently reduced cadmium uptake and accumulation in dwarf Polish wheat (Triticum polonicum L.) - Xing Chen; Shan Yang; Jian Ma; Yiwen Huang; Yi Wang; Jian Zeng; Jun Li; Siyu Li; Dan Long; Xue Xiao; Lina Sha; Dandan Wu; et al. (Journal of Hazardous Materials, 2023)

One-step extraction and solidification of uranium (VI) from sulfate leaching liquor using bifunctional ionic liquids - Fang Zhang; Qiang Wu; Jia-Xuan Yan; Lei-Tao Sha; Yang Li; Xu-Xin Li; Qing-Gang Huang; Ze-Yi Yan (Journal of Environmental Chemical Engineering, 2023)

Quantifying tree canopy coverage threshold of typical residential quarters considering human thermal comfort and heat dynamics under extreme heat - Yingnan Li; Dongli Lin; Yuhan Zhang; Zipeng Song; Xiaohan Sha; Siqi Zhou; Cen Chen; Zhaowu Yu (Building and Environment, 2023)

[Cuproptosis-related immune gene signature predicts clinical benefits from anti-PD-1/PD-L1 therapy in non-small-cell lung cancer - Linfeng Luo; Anlin Li; Sha Fu; Wei Du; Li-Na He; Xuanye Zhang; Yixing Wang; Yixin Zhou; Yang Yunpeng; Zhang Li; Shaodong Hong (Immunologic Research, 2023)

Anti-biofilm and bacteriostatic effects of three flavonoid compounds on Streptococcus mutans - Li Yan; Sha Zhang; Xiaoying Zhou; Shuge Tian (Biofouling, 2023)

MUSER and IPS telescopes for solar and space weather observations - Yihua Yan; Wei Wang; Linjie Chen; Fei Liu; Jin Fan; Zhijun Chen; Lihong Geng; Chengming Tan; Suli Ma; Sha Li; Cang Su; Jing Du; et al. (Advances in Space Research, 2023)

Maternal exposure to 4-vinylcyclohexene diepoxide during pregnancy induces subfertility and birth defects of offspring in mice - Wei Song; Ang Li; Qian-Qian Sha; Shao-Yuan Liu; Yong Zhou; Chang-Yin Zhou; Xue Zhang; Xiao-Zhen Li; Jia-Xin Jiang; Fei Li; Chao Li; Heide Schatten; et al. (Science of The Total Environment, 2023)

Genomic analysis of Marinimicrobium sp. C6131 reveals its genetic potential involved in chitin metabolism - Yan-Ru Dang; Xiao-Yu Zhang; Sha-Sha Liu; Ping-Yi Li; Xue-Bing Ren; Qi-Long Qin (Marine Genomics, 2023)

Investigation into biochar supported Fe-Mo carbides catalysts for efficient biomass gasification tar cracking - Shuping Zhang; Jiaxing Wang; Lei Ye; Sha Li; Yinhai Su; Huiyan Zhang (Chemical Engineering Journal, 2023)

Tumor microenvironment activated nanoreactors for chemiluminescence imaging-guided simultaneous elimination of breast tumors and tumor-resident intracellular pathogens - Xinxin Li; Ting Wu; Zefan Zhang; Sha Liu; Hongmei Cui; Zhongxiong Fan; Baodui Wang; Jun Hai (Chemical Engineering Journal, 2023)

Isolation, characterization and functional validation of a soybean transcription factor, GmDof4.2 improves drought tolerance in transgenic tobacco - Ying Zhai; Jiongxin Chen; Jiaqi He; Jun Zhang; Wei Sha; Haiwei Yu; Yan Zhao; Tianyi Ma; Tianguo Sun; Meijuan Zhang; Shanshan Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Evaluation of data pre-processing and regression models for precise estimation of soil organic carbon using Vis–NIR spectroscopy - Yaxin Wang; Sha Yang; Xiaobin Yan; Chenbo Yang; Meichen Feng; Lujie Xiao; Xiaoyan Song; Meijun Zhang; Fahad Shafiq; Hui Sun; Guangxin Li; Wude Yang; et al. (Journal of Soils and Sediments, 2023)

Variations in the NSP4 gene of the type 2 porcine reproductive and respiratory syndrome virus isolated in China from 1996 to 2021 - Huiyang Sha; Hang Zhang; Qin Luo; Yajie Zheng; Qingge Zhu; Nina Wang; Limei Qin; Huawei Li; Liangzong Huang; Mengmeng Zhao (Virus Genes, 2023)

Retraction Note: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2023)

Iron-calcium reinforced solidification of arsenic alkali residue in geopolymer composite: Wide pH stabilization and its mechanism - Yingfei Sun; Pan Zhang; Zhen Li; Jing Chen; Yan Ke; Jingping Hu; Bingchuan Liu; Jiakuan Yang; Sha Liang; Xintai Su; Huijie Hou (Chemosphere, 2023)

Study on sex-linked region and sex determination candidate gene using a high-quality genome assembly in yellow drum - Sha Sun; Chaowei Song; Fang Han; Qiwei He; Jieping Liu; Sen Zhang; Wei Han; Kun Ye; Zhaofang Han; Zhiyong Wang; Wanbo Li (Aquaculture, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Eocene to Miocene Charophytes from the Qaidam Basin on the northern Tibetan Plateau and its calibration to the Geomagnetic Polarity Time Scale - Yi Xing; Bowen Song; Ting Li; Sha Li; Kui Yan; Qifei Wang; Haichun Zhang; Xiaoqiao Wan (Review of Palaeobotany and Palynology, 2023)

Stilbenes with potent cytotoxicity from the seedcases of Paeonia suffruticosa Andrews - Meng-Yue Yang; Zhao-Xiang Shao; Yue-Tong Wang; Yong-Lian Hou; Ding-Kang Zhu; Sha Chen; Ya-Hui Zhang; Fei Cao; Yong-Kui Jing; Bin Lin; Zhan-Lin Li; Da-Hong Li; et al. (Phytochemistry, 2023)

Fine particulate pollution driven by nitrate in the moisture urban atmospheric environment in the Pearl River Delta region of south China - Jun Tao; Junjun Huang; Guojian Bian; Leiming Zhang; Zhen Zhou; Zhisheng Zhang; Jiawei Li; Yucong Miao; Ziyang Yuan; Qinge Sha; Linhai Xiao; Boguang Wang (Journal of Environmental Management, 2023)

Traceability and identification of fish gelatin from seven cyprinid fishes by high performance liquid chromatography and high-resolution mass spectrometry - Xiao-Mei Sha; Wen-Li Jiang; Zi-Zi Hu; Li-Jun Zhang; Zuo-Hua Xie; Ling Lu; Tao Yuan; Zong-Cai Tu (Food Chemistry, 2023)

A sensitive and quantitative immunochromatographic assay for simultaneous detection of three stimulant laxatives in slimming food - Sha Chen; Tian Guan; Zhenjie Qian; Qiqi Quan; Jin Wang; Xiangmei Li; Shaozong Wu; Yiyong Yan; Xiaojun Yao; Shiwei Zhang; Hongtao Lei (Food Chemistry, 2023)

FeCl3 and Fe2(SO4)3 differentially reduce Cd uptake and accumulation in Polish wheat (Triticum polonicum L.) seedlings by exporting Cd from roots and limiting Cd binding in the root cell walls - Qin Yao; Weiping Li; Ying Liu; Yiran Cheng; Xue Xiao; Dan Long; Jian Zeng; Dandan Wu; Lina Sha; Xing Fan; Houyang Kang; Haiqin Zhang; et al. (Environmental Pollution, 2023)

A biomass-based bilayer aerogel for efficient solar-driven steam production and electricity generation - Lingxuan Bai; Hanxiao Zhang; Rui Lou; Jianzong Li; Mingchao Chi; Jiulong Sha; Xuelian Zhou (Chemical Engineering Journal, 2023)

All-Ceramic, compressible and scalable nanofibrous aerogels for subambient daytime radiative cooling - Tao Li; Haoyang Sun; Meng Yang; Chentao Zhang; Sha Lv; Bin Li; Longhao Chen; Dazhi Sun (Chemical Engineering Journal, 2023)

Andrographolide ameliorates hepatic steatosis by suppressing FATP2-mediated fatty acid uptake in mice with nonalcoholic fatty liver disease - Li-Sha Ran; Ya-Zeng Wu; Yi-Wen Gan; Hong-Lian Wang; Li-Juan Wu; Chun-Mei Zheng; Yao Ming; Ran Xiong; Yong-Lin Li; Shi-Hang Lei; Xue Wang; Xiao-Qing Lao; et al. (Journal of Natural Medicines, 2023)
Excessive intrahepatocellular lipid accumulation or steatosis is caused by abnormal lipid metabolism and a common character of nonalcoholic fatty liver disease (NAFLD), which may progress into cirrhosis and hepatocellular cancer. Andrographolide (Andro) is the primary active ingredient extracted from Andrographis paniculata , showing a protective role against dietary steatosis with the mechanism not fully understood. In this study, we showed that administration of Andro (50, 100, and 200 mg/kg/day for 8 weeks, respectively) attenuated obesity and metabolic syndrome in high-fat diet (HFD)-fed mice with improved glucose tolerance, insulin sensitivity, and reduced hyperinsulinemia, hyperglycemia, and hyperlipidemia. HFD-fed mice presented hepatic steatosis, which was significantly prevented by Andro. In vitro, Andro decreased the intracellular lipid droplets in oleic acid-treated LO2 cells. The selected RT-PCR array revealed a robust expression suppression of the fatty acid transport proteins (FATPs) by Andro treatment. Most importantly, we found that Andro consistently reduced the expression of FATP2 in both the oleic acid-treated LO2 cells and liver tissues of HFD-fed mice. Overexpression of FATP2 abolished the lipid-lowering effect of Andro in oleic acid-treated LO2 cells. Andro treatment also reduced the fatty acid uptake in oleic acid-treated LO2 cells, which was blunted by FATP2 overexpression. Collectively, our findings reveal a novel mechanism underlying the anti-steatosis effect of Andro by suppressing FATP2-mediated fatty acid uptake, suggesting the potential therapeutic application of Andro in the treatment of NAFLD. Graphical abstract

A two-step downscaling method for high-scale super-resolution of daily temperature — a case study of Wei River Basin, China - Xue Li; Yingyin Zhou; Man Zhang; Jian Sha; Zhong-Liang Wang (Environmental Science and Pollution Research, 2022)

Network pharmacological investigation into the mechanism of Kaixinsan powder for the treatment of depression - Li-Jing Du; Xin-Ning Zhang; Sha-Sha Li; Yuan-Fang Sun; Hui-Zi Jin; Shi-Kai Yan; Chuan-Gang Han (Metabolic Brain Disease, 2022)

Dynamic evaluation of environmental impact for three-way catalytic converter with temporal variation life cycle method - Yingying Liu; Hanbing Li; Sha Chen; Yana Zhang; He Lv; Shuqi Yan; Yipei Li; Zunwen Liu (The International Journal of Life Cycle Assessment, 2022)

A comprehensive review on coupled processes and mechanisms of soil-vegetation-hydrology, and recent research advances - Zhongkai Li; Xiaoyan Li; Sha Zhou; Xiaofan Yang; Yongshuo Fu; Chiyuan Miao; Shuai Wang; Guanghui Zhang; Xiuchen Wu; Chao Yang; Yuanhong Deng (Science China Earth Sciences, 2022)

A two-year (2020–2021) observation of marine phycotoxins in phytoplankton in typical mariculture areas of East China Sea - Xiaoqing Tian; Chengqi Fan; Yunyu Tang; Haiyan Zhang; Wei Kang; Sha Chen; Chongbin Li; Ya’nan Lu (Journal of Oceanology and Limnology, 2022)

The role of ancestral seascape discontinuity and geographical distance in structuring rockfish populations in the Pacific Northwest - Cheng-He Sun; Rodolphe Elie Gozlan; Ting Wu; Dan Xue; Ye-Ling Lao; Jian-Feng Yu; Xiao-Shu Zeng; Sha Li; Emilie A. Hardouin; Demetra Andreou; Qun Zhang (Frontiers in Marine Science, 2022)
Despite the apparent absence of physical barriers in the ocean to prevent dispersal, recent studies have highlighted the importance of biological, geographical, physical, and historical barriers in the genetic structuring of marine species populations. This representation is essential for the sustainable exploitation of natural marine resources and for the setup of efficient protected area networks for the conservation of marine species. In this study, we used extensive sampling of Sebastiscus marmoratus , a commercially important inshore rockfish with high site fidelity, to characterize their population genetic structure along the China–Japan coast and to determine the effect of past geological and current biological–physical barriers on the current genetic footprint. A 461-bp fragment of the mtDNA hypervariable portion control region was sequenced for 675 individuals from 15 geographical locations. A total of 292 haplotypes were identified. The population of S. marmoratus showed high haplotype and nucleotide diversity. Pairwise fixation index ( F ST ) and analysis of molecular variance (AMOVA) revealed significant genetic differentiation among populations. The Bayesian skyline plots and neutrality statistics showed a sudden expansion of the S. marmoratus population around the Pleistocene. The Beibu Gulf group had the lowest mean number of pairwise differences, the lowest significant genetic differentiation, and the lowest haplotype and nucleotide diversity, and should be prioritized for protection in the future. Ocean currents, seascape discontinuity, geographical distance, and ecological characteristics may play an important role in shaping the contemporary phylogeographical patterns and population structures of S. marmoratus .

Notch1 down-regulation in lineage-restricted niches is involved in the development of mouse eccrine sweat glands - Yuzhen Wang; Bin Yao; Xianlan Duan; Jianjun Li; Wei Song; Enhejirigala; Zhao Li; Xingyu Yuan; Yi Kong; Yijie Zhang; Xiaobing Fu; Sha Huang (Journal of Molecular Histology, 2022)

MilR3, a unique SARP family pleiotropic regulator in Streptomyces bingchenggensis - Yu-Si Yan; Yun-Qi Yang; Li-Sha Zhou; Ling Zhang; Hai-Yang Xia (Archives of Microbiology, 2022)

Abrupt fluctuations in North Pacific Intermediate Water modulated changes in deglacial atmospheric CO2 - Yanguang Liu; Yue Qiu; Dongling Li; Antonina V. Artemova; Yuying Zhang; Aleksandr A. Bosin; Sergey A. Gorbarenko; Qingsong Liu; Debo Zhao; Longbin Sha; Yi Zhong (Frontiers in Marine Science, 2022)
As a major reservoir of heat and CO 2 , the Pacific Ocean is an important component of the global climate system, but the nature of its circulation under different climatic conditions remains poorly understood. We present sedimentary records of surface water hydrography and nutrient dynamics from the subarctic Pacific Ocean, with the aim of investigating changes in sea-ice coverage, biological productivity, and sea surface temperature in the subarctic Northwest Pacific since 32 kyr. Our records indicate an enhanced North Pacific surface water stratification from the last glacial to Heinrich Stadial 1, which generally limited the siliceous productivity supply to the surface water. A productivity peak during the Bølling/Allerød warm interval was associated with an increase in the atmospheric p CO 2 , and it was driven by the increased supply of nutrient- and CO 2 -rich waters. This process can be attributed to the collapse of the North Pacific Intermediate Water formation at the onset of the Bølling/Allerød interstadial. Moreover, a northward shift of the westerly winds and the gyre boundary could have modulated the expansion of the subpolar gyre, driving changes in poleward heat transport, biogeochemistry, and the hydroclimate of the North Pacific. Our results are consistent with modern evidence for a northward shift of the westerlies in response to global warming, which will likely result in CO 2 outgassing from the subarctic Pacific Ocean in the future.

Insights into adaptive divergence of Japanese mantis shrimp Oratosquilla oratoria inferred from comparative analysis of full-length transcriptomes - Jiao Cheng; Liwen Zhang; Min Hui; Yuan Li; Zhongli Sha (Frontiers in Marine Science, 2022)
The heterogeneous seascapes in the northwestern Pacific (NWP) can be important selective forces driving adaptive divergence of marine coastal species distributed along the gradients. Here, we tested this hypothesis in Japanese mantis shrimp ( Oratosquilla oratoria ) with a wide distribution in the NWP and a significant north-south population structure. To this end, the full-length (FL) transcriptomes of northern and southern O. oratoria were firstly sequenced using PacBio single molecule real-time sequencing technology. Based on the FL transcriptome data, we captured large-scale FL transcripts of O. oratoria and predicted the FL transcriptome structure, including coding region, transcription factor and long noncoding RNA. To reveal the divergence between northern and southern O. oratoria , we identified 2,182 pairs of orthologous genes and inferred their sequence divergences. The average differences in coding, 5’ untranslated and 3’ untranslated region were 1.44%, 2.79% and 1.46%, respectively, providing additional support to previous proposition that northern and southern O. oratoria are two species. We provided further evolutionary context to our analysis by identifying positive selected genes (PSGs) between northern and southern O. oratoria . In total, 98 orthologs were found evolving under positive selection and involved several environmentally responsive genes associated with stress response, immunity and cytoskeletal organization, etc. Furthermore, we found PSGs also diverged in gene expression response of northern and southern O. oratoria to heat stress. These findings not only highlight the importance of genetic variation in these genes in adapting to environmental changes in O. oratoria , but also suggest that natural selection may act on the plasticity of gene expression to facilitate O. oratoria adaptation to environmental gradients. Overall, our work contributes to understanding how marine coastal species has evolved to adapt to heterogeneous seascapes in the NWP.

ML323, a USP1 inhibitor triggers cell cycle arrest, apoptosis and autophagy in esophageal squamous cell carcinoma cells - Yaxin Sun; Beibei Sha; Wenjing Huang; Miaomiao Li; Shan Zhao; Yuan Zhang; Jie Yan; Zheng Li; Jingwen Tang; Peiyan Duan; Jianxiang Shi; Pei Li; et al. (Apoptosis, 2022)

Armochaetoglasins J and K: new cytochalasans from Chaetomium globosum - Li Cheng; Xi Zheng; Qin Li; Meng-Sha Wei; Chun-Mei Chen; Hu-Cheng Zhu; Chang-Li Zeng; Xin-Cai Hao; Yong-Hui Zhang (Natural Product Research, 2022)

Erratum to: Generating broad-spectrum tolerance to ALS-inhibiting herbicides in rice by base editing - Rui Zhang; Sha Chen; Xiangbing Meng; Zhuangzhuang Chai; Delin Wang; Yuge Yuan; Kunling Chen; Linjian Jiang; Jiayang Li; Caixia Gao (Science China Life Sciences, 2022)

A Shuttling Protein Kank1 Plays Important Role in the Sex Determination in Yellow Drum - Sha Sun; Jieping Liu; Sen Zhang; Qiwei He; Wei Han; Kun Ye; Fang Han; Wanbo Li; Zhiyong Wang (Frontiers in Marine Science, 2022)
Sex is one of the most important scientific topics, and the existence of sex dimorphism is a conserved feature in vertebrate taxa. The research on sex-determining genes and sex chromosome evolution is a hot topic in biology. The majority of sex-determining genes expressed in somatic cells, and reciprocal interactions between germ cells and somatic cells, are important for gonadal differentiation. However, the knowledge of how signals are transmitted between somatic cells and germ cells remains unclear. In this study, we confirmed the 36 dph was a sex determination critical stage in yellow drum through transcriptome analysis at the early development stages. We further found that Kank1 participated in the germ cells’ motility process in yellow drum through KEGG pathway analysis together with protein-protein interaction network. With the dual-luciferase reporter assay, we detected that Kank1 increased the transcription of dmrt1_Luc gene in CHO cells and 293T cells. Additionally, we observed that Kank1 was not only expressed in the cytoplasm but also in the nucleus in CHO cells through a fluorescence microscope. These results suggest that Kank1 acts as a shuttling protein as in humans and may play a difunctional role at the early gonad development stage in yellow drum, and it not only participated in the germ cells’ motility but also increased the expression of dmrt1 in yellow drum.

Monitoring soil salinization and its spatiotemporal variation at different depths across the Yellow River Delta based on remote sensing data with multi-parameter optimization - Tiantian Cheng; Jiahua Zhang; Sha Zhang; Yun Bai; Jingwen Wang; Shuaishuai Li; Tehseen Javid; Xianglei Meng; Til Prasad Pangali Sharma (Environmental Science and Pollution Research, 2022)

Activating PIK3CA postzygotic mutations in segmental overgrowth of muscles with bone involvement in the body extremities - Wen Tian; Liying Sun; Qi Zhang; Junhui Zhao; Yang Guo; Wenyao Zhong; Liu Liu; Katia Meirelles; Sha Tang; Jing Zhang; Yingzhao Huang; Yuehan Yin; et al. (Molecular Genetics and Genomics, 2022)

CcpA mutants influence selective carbon source utilization by changing interactions with target genes in Bacillus licheniformis - Yupeng Zhang; Youran Li; Fengxu Xiao; Hanrong Wang; Liang Zhang; Zhongyang Ding; Sha Xu; Zhenghua Gu; Guiyang Shi (Systems Microbiology and Biomanufacturing, 2022)

Biogeography of culturable marine bacteria from both poles reveals that ‘everything is not everywhere’ at the genomic level - Qi‐Long Qin; Zhi‐Bin Wang; Qian‐Qian Cha; Sha‐Sha Liu; Xue‐Bing Ren; Hui‐Hui Fu; Mei‐Ling Sun; Dian‐Li Zhao; Andrew McMinn; Yin Chen; Xiu‐Lan Chen; Yu‐Zhong Zhang; et al. (Environmental Microbiology, 2022)
Summary Based on 16S rRNA gene analyses, the same bacterial operational taxonomic units (OTUs) are common to both the Arctic and Antarctic oceans, supporting the concept ‘everything is everywhere’. However, whether the same OTUs from both poles have identical genomes, i.e. whether ‘everything is still everywhere’ at the genomic level has not yet been examined systematically. Here, we isolated, sequenced and compared the genomes of 45 culturable marine bacteria belonging to three genera of Salinibacterium , Psychrobacter and Pseudoalteromonas from both polar oceans. The bacterial strains with identical 16S rRNA genes were common to both poles in every genus, and four identical genomes were detected in the genus Salinibacterium from the Arctic region. However, no identical genomes were observed from opposite poles in this study. Our data, therefore, suggest that ‘everything is not everywhere’ at the genomic level. The divergence time between bacteria is hypothesized to exert a strong impact on the bacterial biogeography at the genomic level. The geographical isolation between poles was observed for recently diverged, highly similar genomes, but not for moderately similar genomes. This study thus improves our understanding of the factors affecting the genomic‐level biogeography of marine microorganisms isolated from distant locations.

Hydrogen Sulfide Maintains Good Nutrition and Delays Postharvest Senescence in Postharvest Tomato Fruits by Regulating Antioxidative Metabolism - Ting-Ying Zhong; Gai-Fang Yao; Sha-Sha Wang; Ting-Ting Li; Ke-Ke Sun; Jun Tang; Zhong-Qin Huang; Feng Yang; Yan-Hong Li; Xiao-Yan Chen; Lan-Ying Hu; Hua Zhang; et al. (Journal of Plant Growth Regulation, 2021)

MamZ protein plays an essential role in magnetosome maturation process of Magnetospirillum gryphiswaldense MSR-1 - Sha Wu; Qing Wang; Xu Wang; Ruixue Guo; Tongwei Zhang; Yongxin Pan; Feng Li; Ying Li (Journal of Oceanology and Limnology, 2021)

Qaidamihabitans albus gen. nov., sp. nov., a new member of the family Pseudonocardiaceae, and transfer of Prauserella shujinwangii to Qaidamihabitans gen. nov. as Qaidamihabitans shujinwangii comb. nov. - Li-Sha Tian; Gang-Qiang Jiang; Rui Li; Ping Ni; Chuan-En Li; Hong-Yan Zhang; Juan Wang; Xiao-Ping Zhang; Yun Wang; Shu-Kun Tang (Archives of Microbiology, 2021)

Generating broad-spectrum tolerance to ALS-inhibiting herbicides in rice by base editing - Rui Zhang; Sha Chen; Xiangbing Meng; Zhuangzhuang Chai; Delin Wang; Yuge Yuan; Kunling Chen; Linjian Jiang; Jiayang Li; Caixia Gao (Science China Life Sciences, 2021)

Types, characteristics, distribution, and genesis of pockmarks in the South China Sea: insights from high-resolution multibeam bathymetric and multichannel seismic data - Song Zhu; Xuejie Li; Huodai Zhang; Zhibin Sha; Zhen Sun (International Geology Review, 2021)

Genetic control and phenotypic characterization of panicle architecture and grain yield-related traits in foxtail millet (Setaria italica) - Hui Zhi; Qiang He; Sha Tang; Junjun Yang; Wei Zhang; Huifang Liu; Yanchao Jia; Guanqing Jia; Aiying Zhang; Yuhui Li; Erhu Guo; Ming Gao; et al. (Theoretical and Applied Genetics, 2021)

Resource prediction and assessment based on 3D/4D big data modeling and deep integration in key ore districts of North China - Gongwen Wang; Zhiqiang Zhang; Ruixi Li; Junjian Li; Deming Sha; Qingdong Zeng; Zhenshan Pang; Dapeng Li; Leilei Huang (Science China Earth Sciences, 2021)

Descending Modulation of Spinal Itch Transmission by Primary Somatosensory Cortex - Zi-Han Wu; Han-Yu Shao; Yuan-Yuan Fu; Xiao-Bo Wu; De-Li Cao; Sheng-Xiang Yan; Wei-Lin Sha; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)

Acute associations between air pollution on premature rupture of membranes in Hefei, China - Chao Zhang; Sha Li; Gan-lan Guo; Jing-wen Hao; Peng Cheng; Li-lin Xiong; Shu-ting Chen; Ji-yu Cao; Yu-wen Guo; Jia-hu Hao (Environmental Geochemistry and Health, 2021)

Long-term impact of ambient air pollution on preterm birth in Xuzhou, China: a time series study - Sha Li; Lei Peng; Xiaochang Wu; Geng Xu; Peng Cheng; Jingwen Hao; Zhaohui Huang; Meng Xu; Shuting Chen; Chao Zhang; Jiahu Hao (Environmental Science and Pollution Research, 2021)

Traits, strategies, and niches of liana species in a tropical seasonal rainforest - Qi Liu; Frank J. Sterck; Jiao-Lin Zhang; Arne Scheire; Evelien Konings; Min Cao; Li-Qing Sha; Lourens Poorter (Oecologia, 2021)
Plant functional traits and strategies hold the promise to explain species distribution, but few studies have linked multiple traits to multiple niche dimensions (i.e., light, water, and nutrients). Here, we analyzed for 29 liana species in a Chinese tropical seasonal rainforest how: (1) trait associations and trade-offs lead to different plant strategies; and (2) how these traits shape species’ niche dimensions. Eighteen functional traits related to light, water, and nutrient use were measured and species niche dimensions were quantified using species distribution in a 20-ha plot combined with data on canopy gaps, topographic water availability, and soil nutrients. We found a tissue toughness spectrum ranging from soft to hard tissues along which species also varied from acquisitive to conservative water use, and a resource acquisition spectrum ranging from low to high light capture and nutrient use. Intriguingly, each spectrum partly reflected the conservative–acquisitive paradigm, but at the same time, the tissue toughness and the resource acquisition spectrum were uncoupled. Resource niche dimensions were better predicted by individual traits than by multivariate plant strategies. This suggests that trait components that underlie multivariate strategy axes, rather than the plant strategies themselves determine species distributions. Different traits were important for different niche dimensions. In conclusion, plant functional traits and strategies can indeed explain species distributions, but not in a simple and straight forward way. Although the identification of global plant strategies has significantly advanced the field, this research shows that global, multivariate generalizations are difficult to translate to local conditions, as different components of these strategies are important under different local conditions.

Research on joint inversion method of seismic compressional and shear waves from ocean-bottom nodes - Zhitian Zhang; Sha Song; Qingchun Li (Marine Geophysical Research, 2021)

Experimental Investigation on Physical and Mechanical Properties of Granite Subjected to Cyclic Heating and Liquid Nitrogen Cooling - Guan Rong; Song Sha; Bowen Li; Zhiheng Chen; Ziyang Zhang (Rock Mechanics and Rock Engineering, 2021)

Cellulomonas taurus sp. nov., a novel bacteria with multiple hydrolase activity isolated from livestock, and potential application in wastewater treatment - Sha-Sha Zhang; Jian-Feng Xu; Xiao-LI Sun; Wei Guo; Zeng-Shan Liu (Antonie van Leeuwenhoek, 2021)

EEG-Based Anxious States Classification Using Affective BCI-Based Closed Neurofeedback System - Chao Chen; Xuecong Yu; Abdelkader Nasreddine Belkacem; Lin Lu; Penghai Li; Zufeng Zhang; Xiaotian Wang; Wenjun Tan; Qiang Gao; Duk Shin; Changming Wang; Sha Sha; et al. (Journal of Medical and Biological Engineering, 2021)

Self-Assembled Micelles Improve the Oral Bioavailability of Dihydromyricetin and Anti-Acute Alcoholism Activity - Jing Ye; Sha Bao; Shiying Zhao; Yujing Zhu; Qiao Ren; Rui Li; Xiaohong Xu; Quan Zhang (AAPS PharmSciTech, 2021)

Short-term effects of ambient temperature on preterm birth: a time-series analysis in Xuzhou, China - Peng Cheng; Lei Peng; Jingwen Hao; Sha Li; Chao Zhang; Lianjie Dou; Weinan Fu; Fan Yang; Jiahu Hao (Environmental Science and Pollution Research, 2021)

QTL mapping for foxtail millet plant height in multi-environment using an ultra-high density bin map - Qiang He; Hui Zhi; Sha Tang; Lu Xing; Suying Wang; Haigang Wang; Aiying Zhang; Yuhui Li; Ming Gao; Haijin Zhang; Guoqiu Chen; Shutao Dai; et al. (Theoretical and Applied Genetics, 2021)

Overexpression of GmGolS2-1, a soybean galactinol synthase gene, enhances transgenic tobacco drought tolerance - Shuang Qiu; Jun Zhang; Jiaqi He; Wei Sha; Mingyang Li; Yan Zhao; Ying Zhai (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Experimental Evaluation of Physical and Mechanical Properties of Geothermal Reservoir Rock after Different Cooling Treatments - Song Sha; Guan Rong; Zhiheng Chen; Bowen Li; Ziyang Zhang (Rock Mechanics and Rock Engineering, 2020)

Simultaneous detection of zearalenone, citrinin, and ochratoxin A in pepper by capillary zone electrophoresis - Minghui Li; Zaikang Tong; Xingjun Gao; Lijun Zhang; Sha Li (Food Additives & Contaminants: Part A, 2020)

Carbon emissions in the transportation sector of Yangtze River Economic Belt: decoupling drivers and inequality - Lina Zhang; Donghui Chen; Sha Peng; Qinghua Pang; Fangjuan Li (Environmental Science and Pollution Research, 2020)

Effect of combining urea fertilizer with P and K fertilizers on the efficacy of urease inhibitors under different storage conditions - Zhipeng Sha; Tiantian Lv; Maarten Staal; Xin Ma; Zhang Wen; Qianqian Li; Gregor Pasda; Tom Misselbrook; Xuejun Liu (Journal of Soils and Sediments, 2020)

Identifying common genome-wide risk genes for major psychiatric traits - Sha Liu; Shuquan Rao; Yong Xu; Jun Li; Hailiang Huang; Xu Zhang; Hui Fu; Qiang Wang; Hongbao Cao; Ancha Baranova; Chunhui Jin; Fuquan Zhang (Human Genetics, 2020)

Increased risk of herpes zoster infection in patients with inflammatory bowel disease: a meta-analysis of cohort studies - Longui Ning; Rongqiang Liu; Sha Li; Guodong Shan; Haojie Du; Jie Zhang; Wenguo Chen; Fenming Zhang; Jinghua Yu; Guoqiang Xu (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Isoflurane produces antidepressant effects inducing BDNF-TrkB signaling in CUMS mice - Sha-Sha Zhang; Yu-Hua Tian; Song-Jun Jin; Wen-Cheng Wang; Jing-Xin Zhao; Xiao-Ming Si; Li Zhang; Hong Xu; Jing-Yu Jin (Psychopharmacology, 2019)

Direct micro-electric stimulation alters phenanthrene-degrading metabolic activities of Pseudomonas sp. strain DGYH-12 in modified bioelectrochemical system - Xingbiao Wang; Guilong Wan; Liuyang Shi; Xiaolong Gao; Xiaoxia Zhang; Xiaoguang Li; Jianfang Zhao; Beibei Sha; Zhiyong Huang (Environmental Science and Pollution Research, 2019)

RETRACTED ARTICLE: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2019)

Rheinic acid ameliorates radiation-induced acute enteritis in rats through PPAR-γ/NF-κB - Haixia Sha; Yu Gu; Weixing Shen; Li Zhang; Fei Qian; Yudong Zhao; Haixiao Li; Ting Zhang; Weimin Lu (Genes & Genomics, 2019)

The associations of air pollution exposure during pregnancy with fetal growth and anthropometric measurements at birth: a systematic review and meta-analysis - Li Fu; Yi Chen; Xinyi Yang; Zuyao Yang; Sha Liu; Lei Pei; Baixiang Feng; Ganxiang Cao; Xin Liu; Hualiang Lin; Xing Li; Yufeng Ye; et al. (Environmental Science and Pollution Research, 2019)

Investigation of the oil-seawater mixed flow under an electromagnetic field - Aiwu Peng; Lingzhi Zhao; Xiaoqiang Chen; Qingfan Zhang; Ciwen Sha; Jianping Zhao; Ran Li; Zhaolian Wang (Acta Oceanologica Sinica, 2019)

Cloning, Expression and Characterization of a Highly Active Alcohol Dehydrogenase for Production of Ethyl (S)-4-Chloro-3-Hydroxybutyrate - Yi-Hao Zhu; Cai-Yun Liu; Sha Cai; Li-Bin Guo; In-Won Kim; Vipin C. Kalia; Jung-Kul Lee; Ye-Wang Zhang (Indian Journal of Microbiology, 2019)

Isolation and characterization of microsatellite markers for exploring introgressive hybridization between the Oratosquilla oratoria complex - Jiao Cheng; Nan Zhang; Zhong-li Sha (Molecular Biology Reports, 2018)

Mitochondrial phylogenomics reveals insights into taxonomy and evolution of Penaeoidea (Crustacea: Decapoda) - Jiao Cheng; Tin‐Yam Chan; Nan Zhang; Song Sun; Zhong‐li Sha (Zoologica Scripta, 2018)
The taxonomy and phylogeny of Penaeoidea have long been fraught with controversy. Here, we carried out the first mitochondrial phylogenomic analysis on all the penaeoid families and tribes, including nine newly sequenced and 14 published mitogenomes, towards elucidating the phylogeny and evolutionary history of Penaeoidea. All these nine mitogenomes exhibit the pancrustacean ground pattern, except that Benthonectes filipes contains two additional clusters of tRNA Ala , tRNA Arg and tRNA Asn and an uncommon noncoding region. The resulted phylogenetic tree is generally well resolved with Benthesicymidae sister to Aristeidae, forming a clade with Solenoceridae. Contrary to traditional classification, this clade has a sister relationship with the tribe Penaeini of the family Penaeidae. The family Sicyoniidae is deeply nested within the penaeid tribe Trachypenaeini which forms a sister clade with the remaining penaeid tribe, Parapenaeini. As the family Penaeidae is recovered to be polyphyletic, the three tribes in Penaeidae are all elevated to familial status. On the other hand, the family Sicyoniidae is retained to accommodate Trachypenaeini because they are now synonyms and the former name is more senior. This work is the first molecular analysis concurring with the latest findings in fossil assessments showing that Parapeaneini is the most primitive in Penaeoidae. Our results also illustrate a shallow‐water origin and an onshore–offshore evolutionary shift in penaeoid shrimps.

Terpenoids from the barks of Magnolia maudiae (Dunn) Figlar - Sui Xianjin; Shi Sha; Muge Qi; Zhengxi Zhang; Yuyao Yang; Haibo Wu; Linfeng Li; Wenshu Wang; Anmin Huang (Natural Product Research, 2018)

The influence of drought strength on soil respiration in a woody savanna ecosystem, southwest China - Yuntong Liu; Jing Li; Yanqiang Jin; Yiping Zhang; Liqing Sha; John Grace; Qinghai Song; Wenjun Zhou; Aiguo Chen; Peiguang Li; Shubin Zhang (Plant and Soil, 2018)

Global environmental costs of China's thirst for milk - Zhaohai Bai; Michael R. F. Lee; Lin Ma; Stewart Ledgard; Oene Oenema; Gerard L. Velthof; Wenqi Ma; Mengchu Guo; Zhanqing Zhao; Sha Wei; Shengli Li; Xia Liu; et al. (Global Change Biology, 2018)
China has an ever‐increasing thirst for milk, with a predicted 3.2‐fold increase in demand by 2050 compared to the production level in 2010. What are the environmental implications of meeting this demand, and what is the preferred pathway? We addressed these questions by using a nexus approach, to examine the interdependencies of increasing milk consumption in China by 2050 and its global impacts, under different scenarios of domestic milk production and importation. Meeting China's milk demand in a business as usual scenario will increase global dairy‐related (China and the leading milk exporting regions) greenhouse gas ( GHG ) emissions by 35% (from 565 to 764 Tg CO 2eq ) and land use for dairy feed production by 32% (from 84 to 111 million ha) compared to 2010, while reactive nitrogen losses from the dairy sector will increase by 48% (from 3.6 to 5.4 Tg nitrogen). Producing all additional milk in China with current technology will greatly increase animal feed import; from 1.9 to 8.5 Tg for concentrates and from 1.0 to 6.2 Tg for forage (alfalfa). In addition, it will increase domestic dairy related GHG emissions by 2.2 times compared to 2010 levels. Importing the extra milk will transfer the environmental burden from China to milk exporting countries; current dairy exporting countries may be unable to produce all additional milk due to physical limitations or environmental preferences/legislation. For example, the farmland area for cattle‐feed production in New Zealand would have to increase by more than 57% (1.3 million ha) and that in Europe by more than 39% (15 million ha), while GHG emissions and nitrogen losses would increase roughly proportionally with the increase of farmland in both regions. We propose that a more sustainable dairy future will rely on high milk demanding regions (such as China) improving their domestic milk and feed production efficiencies up to the level of leading milk producing countries. This will decrease the global dairy related GHG emissions and land use by 12% (90 Tg CO 2eq reduction) and 30% (34 million ha land reduction) compared to the business as usual scenario, respectively. However, this still represents an increase in total GHG emissions of 19% whereas land use will decrease by 8% when compared with 2010 levels, respectively.

A 3-D DDA damage analysis of brick masonry buildings under the impact of boulders in mountainous areas - Shu-guang Liu; Zhu-jun Li; Hong Zhang; Wei Wu; Gui-hui Zhong; Sha Lou (Journal of Mountain Science, 2018)

Genomic analysis of a recombinant NADC30-like porcine reproductive and respiratory syndrome virus in china - Lin-jian Wang; Bo Wan; Zhenhua Guo; Songlin Qiao; Rui Li; Sha Xie; Xin-xin Chen; Gaiping Zhang (Virus Genes, 2018)

Effects of neutral phytase on growth performance and phosphorus utilization in crucian carp (Carassius auratus) - Xin-zheng Nie; Sha Chen; Xiao-xu Zhang; Bin-yang Dai; Li-chun Qian (Journal of Zhejiang University-SCIENCE B, 2017)

Comparison of infrared canopy temperature in a rubber plantation and tropical rain forest - Qing-Hai Song; Yun Deng; Yi -Ping Zhang; Xiao-Bao Deng; You-Xing Lin; Li-Guo Zhou; Xue-Hai Fei; Li-Qing Sha; Yun-Tong Liu; Wen-Jun Zhou; Jin-Bo Gao (International Journal of Biometeorology, 2017)

Electrophysiologic Studies on the Risks and Potential Mechanism Underlying the Proarrhythmic Nature of Azithromycin - Mengdan Zhang; Ming Xie; Sha Li; Ying Gao; Shuyin Xue; Huili Huang; Kesu Chen; Fuming Liu; Long Chen (Cardiovascular Toxicology, 2017)

Neural correlates of 12-h abstinence-induced craving in young adult smokers: a resting-state study - Yangding Li; Kai Yuan; Yanzhi Bi; Yanyan Guan; Jiadong Cheng; Yajuan Zhang; Sha Shi; Xiaoqi Lu; Dahua Yu; Jie Tian (Brain Imaging and Behavior, 2017)

The K+/H+ antiporter AhNHX1 improved tobacco tolerance to NaCl stress by enhancing K+ retention - Wei-Wei Zhang; Jing-Jing Meng; Jin-Yi Xing; Sha Yang; Feng Guo; Xin-Guo Li; Shu-Bo Wan (Journal of Plant Biology, 2017)

Fatality risks for nosocomial outbreaks of Middle East respiratory syndrome coronavirus in the Middle East and South Korea - Jianping Sha; Yuan Li; Xiaowen Chen; Yan Hu; Yajin Ren; Xingyi Geng; Zhiruo Zhang; Shelan Liu (Archives of Virology, 2017)

Induced Pluripotent Stem Cells in Huntington’s Disease: Disease Modeling and the Potential for Cell-Based Therapy - Ling Liu; Jin-Sha Huang; Chao Han; Guo-Xin Zhang; Xiao-Yun Xu; Yan Shen; Jie Li; Hai-Yang Jiang; Zhi-Cheng Lin; Nian Xiong; Tao Wang (Molecular Neurobiology, 2016)

Responses of soil inhabiting nitrogen-cycling microbial communities to wetland degradation on the Zoige Plateau, China - Li-sha Wu; Yuan-yang Nie; Zhi-rong Yang; Jie Zhang (Journal of Mountain Science, 2016)

Prescreening, identification and harvesting of microalgae with antibacterial activity - Ang Li; Ling Zhang; Zhen-yu Zhao; Sha-sha Ma; Meng Wang; Ping-huai Liu (Biologia, 2016)

Molecular cytogenetic characterization of a new wheat-rye 1BL•1RS translocation line expressing superior stripe rust resistance and enhanced grain yield - Weiliang Qi; Yao Tang; Wei Zhu; Daiyan Li; Chengdou Diao; Lili Xu; Jian Zeng; Yi Wang; Xing Fan; Lina Sha; Haiqin Zhang; Youliang Zheng; et al. (Planta, 2016)

Characterization of β-glucosidase from Aspergillus terreus and its application in the hydrolysis of soybean isoflavones - Feng-ying Yan; Wei Xia; Xiao-xu Zhang; Sha Chen; Xin-zheng Nie; Li-chun Qian (Journal of Zhejiang University-SCIENCE B, 2016)

Inhibition control impairments in adolescent smokers: electrophysiological evidence from a Go/NoGo study - Junsen Yin; Kai Yuan; Dan Feng; Jiadong Cheng; Yangding Li; Chenxi Cai; Yanzhi Bi; Shi Sha; Xiaomin Shen; Ben Zhang; Ting Xue; Wei Qin; et al. (Brain Imaging and Behavior, 2016)

Microsatellite records for volume 8, issue 2 - Dareen Almojil; Maria Cristina Arias; Rochelle R. Beasley; Yiyong Chen; Rulon W. Clark; Yinghui Dong; Zhiguo Dong; Natalie Forsdick; Elaine Françoso; E. González-Ortegón; A. M. González-Tizón; Linsheng Gui; et al. (Conservation Genetics Resources, 2016)

How does habitat filtering affect the detection of conspecific and phylogenetic density dependence? - Junjie Wu; Nathan G. Swenson; Calum Brown; Caicai Zhang; Jie Yang; Xiuqin Ci; Jie Li; Liqing Sha; Min Cao; Luxiang Lin (Ecology, 2016)
Conspecific negative density dependence ( CNDD ) has been recognized as a key mechanism underlying species coexistence, especially in tropical forests. Recently, some studies have reported that seedling survival is also negatively correlated with the phylogenetic relatedness between neighbors and focal individuals, termed phylogenetic negative density dependence ( PNDD ). In contrast to CNDD or PNDD , shared habitat requirements between closely related individuals are thought to be a cause of observed positive effects of closely related neighbors, which may affect the strength and detectability of CNDD or PNDD . In order to investigate the relative importance of these mechanisms for tropical tree seedling survival, we used generalized linear mixed models to analyze how the survival of more than 10 000 seedlings of woody plant species related to neighborhood and habitat variables in a tropical rainforest in southwest China. By comparing models with and without habitat variables, we tested how habitat filtering affected the detection of CNDD and PNDD . The best‐fitting model suggested that CNDD and habitat filtering played key roles in seedling survival, but that, contrary to our expectations, phylogenetic positive density dependence ( PPDD ) had a distinct and important effect. While habitat filtering affected the detection of CNDD by decreasing its apparent strength, it did not explain the positive effects of closely related neighbors. Our results demonstrate that a failure to control for habitat variables and phylogenetic relationships may obscure the importance of conspecific and heterospecific neighbor densities for seedling survival.

Response of Soil Moisture to Hydro-meteorological Variables Under Different Precipitation Gradients in the Yellow River Basin - Sha Li; Wei Liang; Weibin Zhang; Qinghua Liu (Water Resources Management, 2016)

GPS in pollen tubes: Found! - Sha Li; Yan Zhang (Science China Life Sciences, 2016)

Molecular cloning of HMW glutenin subunits from Roegneria kamoji (Poaceae: Triticeae) - Ying-Xia Lei; Kuai Yu; Yi Wang; Xing Fan; Hou-Yang Kang; Li-Na Sha; Yong-Hong Zhou; Hai-Qin Zhang (Biologia, 2016)

Genome sequencing and analysis of a novel recombinant porcine epidemic diarrhea virus strain from Henan, China - Renfeng Li; Songlin Qiao; Yanyan Yang; Junqing Guo; Sha Xie; Enmin Zhou; Gaiping Zhang (Virus Genes, 2016)

Environmental Enrichment Ameliorates Neonatal Sevoflurane Exposure-Induced Cognitive and Synaptic Plasticity Impairments - Mu-huo Ji; Xing-ming Wang; Xiao-ru Sun; Hui Zhang; Ling-sha Ju; Li-li Qiu; Jiao-jiao Yang; Min Jia; Jing Wu; Jianjun Yang (Journal of Molecular Neuroscience, 2015)

Associations of hypoxia inducible factor-1α gene polymorphisms with susceptibility to digestive tract cancers: a case–control study and meta-analysis - Zhi-Hai Ni; Xian-Jun Liang; Jing-Gang Mo; Yi Zhang; Jian-Hua Liang; Yu-Sha Yang; Yong Zhou; Zhao-Hua Li; Jian-Liang Zhang; Yin-Lu Ding; Peng Zhang; Jin-Qing Wang (Genes & Genomics, 2015)

Attenuated Blood-Brain Barrier Dysfunction by XQ-1H Following Ischemic Stroke in Hyperlipidemic Rats - Weirong Fang; Lan Sha; Nandani Darshika Kodithuwakku; Jie Wei; Rui Zhang; Dan Han; Lishun Mao; Yunman Li (Molecular Neurobiology, 2015)

Soil cellulase activity and fungal community responses to wetland degradation in the Zoige Plateau, China - Li-sha Wu; Su Feng; Yuan-yang Nie; Jian-hong Zhou; Zhi-rong Yang; Jie Zhang (Journal of Mountain Science, 2015)

Spatiotemporal Change of Blue Water and Green Water Resources in the Headwater of Yellow River Basin, China - Weibin Zhang; Xiaochun Zha; Jiaxing Li; Wei Liang; Yugai Ma; Dongmei Fan; Sha Li (Water Resources Management, 2014)

Neural Stem Cell Transplants Improve Cognitive Function Without Altering Amyloid Pathology in an APP/PS1 Double Transgenic Model of Alzheimer’s Disease - Wei Zhang; Pei-Jun Wang; Hong-ying Sha; Jiong Ni; Ming-hua Li; Guo-jun Gu (Molecular Neurobiology, 2014)

From Inducing Autophagy to Programmed Cell Death? The PI3K Functional Domain Study of Protein Latcripin-1 from Lentinula edodes C91-3 - Ben Liu; Siruo Zhang; Mintao Zhong; Li Sha; Yongzhi Lun; Wei Zhang; Xiaoli Wang; Xingyun Li; Jing Cao; Anhong Ning; Min Huang (International Journal of Peptide Research and Therapeutics, 2014)

Combination of a Novel Photosensitizer DTPP with 650 nm Laser Results in Efficient Apoptosis and Cytoskeleton Collapse in Breast Cancer MCF-7 Cells - H. Wang; H. M. Zhang; H. J. Yin; L. Q. Zheng; M. Q. Wei; H. Sha; Y. X. Li (Cell Biochemistry and Biophysics, 2014)

Dynamic alterations of connexin43, matrix metalloproteinase-2 and tissue inhibitor of matrix metalloproteinase-2 during ventricular fibrillation in canine - Jing Wang; Jing-sha Li; Hong-zhen Liu; Shao-lei Yi; Guo-ying Su; Yun Zhang; Jing-quan Zhong (Molecular and Cellular Biochemistry, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Lithium Chloride Alleviates Neurodegeneration Partly by Inhibiting Activity of GSK3β in a SCA3 Drosophila Model - Dan-Dan Jia; Li Zhang; Zhao Chen; Chun-Rong Wang; Feng-Zhen Huang; Ran-Hui Duan; Kun Xia; Bei-Sha Tang; Hong Jiang (The Cerebellum, 2013)

Molecular characterization of a porcine kobuvirus variant strain in China - Da Shi; Sha Zhang; Jianfei Chen; Hongyan Shi; Xin Zhang; Li Feng (Archives of Virology, 2013)

Prevalence of hepatitis B virus and hepatitis C virus in patients with human immunodeficiency virus infection in central China - Xi Chen; Jian-Mei He; Li-Sha Ding; Guo-Qiang Zhang; Xiao-Bai Zou; Jun Zheng (Archives of Virology, 2013)

Development of In Vitro Macrophage System to Evaluate Phagocytosis and Intracellular Fate of Penicillium marneffei Conidia - Sha Lu; Yongxuan Hu; Changming Lu; Junmin Zhang; Xiqing Li; Liyan Xi (Mycopathologia, 2013)

Chromoblastomycosis in Mainland China: A Systematic Review on Clinical Characteristics - Sha Lu; Changming Lu; Junmin Zhang; Yongxuan Hu; Xiqing Li; Liyan Xi (Mycopathologia, 2013)

Melanin in a Meristematic Mutant of Fonsecaea monophora Inhibits the Production of Nitric Oxide and Th1 Cytokines of Murine Macrophages - Junmin Zhang; Li Wang; Liyan Xi; Huaiqiu Huang; Yongxuan Hu; Xiqing Li; Xiao Huang; Sha Lu; Jiufeng Sun (Mycopathologia, 2013)

Genome-wide association study identified novel genetic variant on SLC45A3 gene associated with serum levels prostate-specific antigen (PSA) in a Chinese population - Jielin Sun; Sha Tao; Yong Gao; Tao Peng; Aihua Tan; Haiying Zhang; Xiaobo Yang; Xue Qin; Yanling Hu; Junjie Feng; Seong-Tae Kim; Xiaoling Lin; et al. (Human Genetics, 2013)

Molecular Cloning and Characterization of Two 9-Lipoxygenase Genes from Taxus chinensis - Shu-tao Li; Meng Zhang; Chun-hua Fu; Sha Xie; Yu Zhang; Long-jiang Yu (Plant Molecular Biology Reporter, 2012)

Effects of Formaldehyde Stress on Physiological Characteristics and Gene Expression Associated with Photosynthesis in Arabidopsis thaliana - Sha-Sha Wang; Zhong-Bang Song; Zhen Sun; Jing Zhang; Yan Mei; Hong-Juan Nian; Kun-Zhi Li; Li-Mei Chen (Plant Molecular Biology Reporter, 2012)

A fully automatic registration approach based on contour and SIFT for HJ-1 images - XiLiang Ni; ChunXiang Cao; Lin Ding; Tao Jiang; Hao Zhang; HuiCong Jia; GuangHe Li; Jian Zhao; Wei Chen; Wei Ji; Min Xu; MengXu Gao; et al. (Science China Earth Sciences, 2012)

Enhancing Taxol Biosynthesis by Overexpressing a 9-Cis-Epoxycarotenoid Dioxygenase Gene in Transgenic Cell Lines of Taxus chinensis - Shu-tao Li; Chun-hua Fu; Meng Zhang; Yu Zhang; Sha Xie; Long-jiang Yu (Plant Molecular Biology Reporter, 2012)

Molecular and cytological evidences for the natural wheatgrass hybrids occurrence and origin in west China - Jian Zeng; Xing Fan; Hai-Qin Zhang; Li-Na Sha; Hou-Yang Kang; Li Zhang; Rui-Wu Yang; Chun-Bang Ding; Yong-Hong Zhou (Genes & Genomics, 2012)

Identification, fine mapping and characterization of Rht-dp, a recessive wheat dwarfing (reduced height) gene derived from Triticum polonicum - Hou-Yang Kang; Li-Juan Lin; Zhi-Jian Song; Jing-Ya Yuan; Mei-Yu Zhong; Hai-Qin Zhang; Xing Fan; Li-Na Sha; Yi Wang; Li-Li Xu; Jian Zeng; Yong-Hong Zhou (Genes & Genomics, 2012)

Overexpressions of dihydroxyacetone synthase and dihydroxyacetone kinase in chloroplasts install a novel photosynthetic HCHO-assimilation pathway in transgenic tobacco using modified Gateway entry vectors - Su-Qin Xiao; Zhen Sun; Sha-Sha Wang; Jing Zhang; Kun-Zhi Li; Li-Mei Chen (Acta Physiologiae Plantarum, 2012)

Phylogeny and molecular evolution of the DMC1 gene within the StH genome species in Triticeae (Poaceae) - Xiao-Li Wang; Xing Fan; Jian Zeng; Li-Na Sha; Hai-Qin Zhang; Hou-Yang Kang; Rui-Wu Yang; Li Zhang; Chun-Bang Ding; Yong-Hong Zhou (Genes & Genomics, 2012)

Erratum to: Physiological and transcriptional analysis of the effects of formaldehyde exposure on Arabidopsis thaliana - Sha-Sha Wang; Zhong-Bang Song; Zhen Sun; Jing Zhang; Yan Mei; Hong-Juan Nian; Kun-Zhi Li; Li-Mei Chen (Acta Physiologiae Plantarum, 2012)

Physiological and transcriptional analysis of the effects of formaldehyde exposure on Arabidopsis thaliana - Sha-Sha Wang; Zhong-Bang Song; Zhen Sun; Jing Zhang; Yan Mei; Hong-Juan Nian; Kun-Zhi Li; Li-Mei Chen (Acta Physiologiae Plantarum, 2012)

Isolation of Penicillium marneffei From Soil and Wild Rodents in Guangdong, SE China - Xiqing Li; Yabo Yang; Xia Zhang; Xianyi Zhou; Sha Lu; Li Ma; Changming Lu; Liyan Xi (Mycopathologia, 2011)

Gastric motility functional study based on electrical bioimpedance measurements and simultaneous electrogastrography - Zhang-yong Li; Chao-shi Ren; Shu Zhao; Hong Sha; Juan Deng (Journal of Zhejiang University-SCIENCE B, 2011)

The unsaturation of phosphatidylglycerol in thylakoid membrane alleviates PSII photoinhibition under chilling stress - Xiao-lin Sun; Sha Yang; Li-Yan Wang; Qiu-Yu Zhang; Shi-Jie Zhao; Qing-Wei Meng (Plant Cell Reports, 2011)

Genome-wide analysis of OCT4 binding sites in glioblastoma cancer cells - Xue-feng Fang; Wei-yi Zhang; Na Zhao; Wei Yu; Dong Ding; Xu Hong; Li-sha Li; Hua-rong Zhang; Shu Zheng; Biao-yang Lin (Journal of Zhejiang University-SCIENCE B, 2011)

Quantitative estimation of the shrub canopy LAI from atmosphere-corrected HJ-1 CCD data in Mu Us Sandland - Wei Chen; ChunXiang Cao; QiSheng He; HuaDong Guo; Hao Zhang; RenQiang Li; Sheng Zheng; Min Xu; MengXu Gao; Jian Zhao; Sha Li; XiLiang Ni; et al. (Science China Earth Sciences, 2010)

Construction of Two BAC Libraries from Half-Smooth Tongue Sole Cynoglossus semilaevis and Identification of Clones Containing Candidate Sex-Determination Genes - Chang-Wei Shao; Song-Lin Chen; Chantel F. Scheuring; Jian-Yong Xu; Zhen-Xia Sha; Xiao-Li Dong; Hong-Bin Zhang (Marine Biotechnology, 2010)

A single residue mutation of 5-enoylpyruvylshikimate-3-phosphate synthase in Pseudomonas stutzeri enhances resistance to the herbicide glyphosate - Aimin Liang; Jiying Sha; Wei Lu; Ming Chen; Liang Li; Dan Jin; Yongliang Yan; Jin Wang; Shuzhen Ping; Wei Zhang; Yiding Wang; Min Lin (Biotechnology Letters, 2008)

Molecular identification and the complete nucleotide sequence of TYLCV isolate from Shanghai of China - Zhang Yongping; Zhu Weimin; Cui Huimei; Qiu Yang; Sha Kun; Wan Yanhui; Zhu Longying; Yu Li; Hui Zhang (Virus Genes, 2008)

Identification of a New Gene Encoding EPSPS with High Glyphosate Resistance from the Metagenomic Library - Dan Jin; Wei Lu; Shuzhen Ping; Wei Zhang; Jian Chen; Baoqing Dun; Ruiqiang Ma; Zhonglin Zhao; Jiying Sha; Liang Li; Zhirong Yang; Ming Chen; et al. (Current Microbiology, 2007)

Rapid Evolution, Genetic Variations, and Functional Association of the Human Spermatogenesis-Related Gene NYD-SP12 - Qü Zhang; Feng Zhang; Xiao-hua Chen; Yin-qiu Wang; Wei-qi Wang; Alice A. Lin; Luca L. Cavalli-Sforza; Li Jin; Ran Huo; Jia-hao Sha; Zheng Li; Bing Su (Journal of Molecular Evolution, 2007)